Moisture power generation device

By adopting a multi-layer functional layer in the moisture power generation device, and using the first sub-layer as a moisture reservoir to provide moisture to the second sub-layer, the problem of unstable electrical output of the moisture power generation device in the prior art under low humidity conditions is solved, and the stable electrical output under different humidity conditions is achieved, which is suitable for power supply to high-power devices.

CN119968721APending Publication Date: 2025-05-09AUSTRALIAN ADVANCED MATERIALS PTY LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380069110.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2023-07-27
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing humidity power generation devices show stable electrical output under high humidity conditions, but the electrical output is instantly unstable under low humidity conditions, making it difficult to be suitable for power supply to high-power devices.

Method used

A moisture power generation device is designed, employing a functional layer structure including at least two sub-layers, wherein the first sub-layer acts as a moisture reservoir, providing moisture to the second sub-layer, which generates charge carriers after obtaining moisture. The device maintains moisture delivery to the functional sublayer by absorbing and releasing water molecules inside the moisture reservoir sublayer under different humidity conditions, reducing dependence on ambient moisture conditions.

Benefits of technology

It realizes maintaining a relatively stable electrical output under different humidity conditions, improves the performance of the device under changing ambient humidity conditions, and is suitable for power supply to high-power devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119968721A_ABST
    Figure CN119968721A_ABST
Patent Text Reader

Abstract

A moisture power generation device includes: a first electrode and a second electrode; and a functional layer disposed between the first electrode and the second electrode, the functional layer releasing charge carriers; the functional layer comprises at least two sub-layers; a first sub-layer acting as a moisture reservoir to a second sub-layer to provide moisture to the second sub-layer; and a second sub-layer, the second sub-layer generating charge carriers according to moisture that can be obtained from the first sub-layer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This patent application claims priority to Australian patent application No. 2022902105 filed on July 27, 2022 and Australian patent application No. 2023901264 filed on April 28, 2023, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0002] The present invention relates to a moisture electric generating device, and in particular, to a moisture electric generating device including a layer serving as a moisture reservoir. Background Art

[0003] Due to the shortage of traditional energy sources, collecting green energy from the environment plays a vital role in the development of future energy supply. Moisture is one of the most abundant green energy sources, which has yet to be used for energy collection and conversion from thermal energy to electricity. Recently, moisture generators (MEGs) with ionized groups or polar bonds in nanomaterials have been widely studied to collect energy from moisture in the environment and convert it into electricity through moisture absorption and ion migration. For example, oxygen functional groups in the surface of carbon nanomaterials interact with water molecules from moisture and dissociate the water molecules to generate mobile hydrogen ions. Therefore, more hydrogen ions in the outer layer exposed to moisture contribute to the concentration difference of hydrogen ions for potential. In addition, MEG has also been shown to be used as a wearable device by collecting moisture from breath or the environment, which presents great potential in self-powered wearable devices.

[0004] Generally, metal oxides (TiO2) and carbon-based materials (graphene oxide, polymers) are used for MEG because polar bonds or oxygen-containing groups (-OH and -COOH) can absorb H + ions and induce electrical potential. In particular, graphene oxide (GO) shows high specific surface area, abundant oxygen-containing groups and good mechanical properties, which exhibits rapid moisture absorption and stable electrical output. In addition, GO is modified with oxygen-containing groups or internal structures to further improve its electrical output. In recent studies, graphene oxide-based flexible MEG was fabricated with a 0.8 mm 2 The small size of MEG exhibits an open circuit voltage of 0.7 V. However, the voltage or current of MEG is closely related to the relative humidity (RH) in the environment and shows an instantaneous output, which inhibits its widespread application in generators. In addition, the electrical output of MEG requires further improvement to make it suitable for powering devices with high power. In order to better understand its fabrication and application for future powering devices, the mechanism of power generation and enhancement should also be studied. Summary of the invention

[0005] According to one embodiment, a moisture power generation device includes: a first electrode and a second electrode; and a functional layer arranged between the first electrode and the second electrode, the functional layer releasing charge carriers; the functional layer includes at least two sublayers: a first sublayer, which acts as a moisture reservoir to the second sublayer to provide moisture to the second sublayer; and the second sublayer, which generates charge carriers based on the moisture that can be obtained from the first sublayer.

[0006] Including a water / moisture reservoir sublayer in a moisture power generation (MEG) device helps control the delivery of moisture to the second (functional) sublayer. The functional sublayer may also be referred to as an active sublayer. The functional sublayer releases charge when it absorbs moisture. For example, the functional groups of the functional layer generate charge carriers by dissociating water molecules of moisture. The moisture reservoir provides delivery of moisture to the functional sublayer that is less dependent on ambient moisture conditions because it contains water molecules inside itself. The moisture power generation device can generate charge under low humidity conditions and high humidity conditions, for example, water in the moisture reservoir sublayer will evaporate at low humidity, and it will absorb water at high humidity. This can help make the performance of the MEG device less variable under changing ambient moisture conditions because moisture delivery to the functional sublayer can be maintained.

[0007] The sublayer is capable of retaining moisture, and it can act as a pool to other layers in the moisture power generation device by providing moisture to these other layers. It acts as a moisture source to other sublayers in the moisture power generation device. The sublayer that acts as a moisture reservoir can also be called a hydration layer because it can hydrate the other sublayers. The advantage of providing a sublayer that acts as a moisture reservoir to the second sublayer is that it can hydrate the second sublayer. Moisture can be provided from the first sublayer to the second sublayer, which means that the second sublayer can be hydrated even under low humidity environmental conditions. Therefore, due to the abundant water in the first sublayer, the first sublayer can help hydrate the second sublayer under ambient conditions or even under extreme conditions (0% RH). The water reservoir sublayer acts like a pool that can release water at low humidity and store water at high humidity.

[0008] The sublayers may have different primary functions, the first sublayer acting as a moisture reservoir (hydration layer) for the second sublayer and the second sublayer acting as a functional (active) layer to dissociate charge carriers upon absorption of moisture.

[0009] In other embodiments, the first sublayer includes a polymer.

[0010] The polymer can be hydrated to include a high water content. The polymer can be an efficient moisture absorber, meaning that moisture can be absorbed into the moisture power generation device even in a low humidity environment. This allows moisture to be more easily absorbed into the moisture power generation device compared to an example with a single non-polymer functional layer (such as GO). This efficient moisture absorption property allows moisture power generation to absorb water in a low humidity environment and improve the electrical performance of the device in a low humidity environment. Examples of polymers include 4-styrenesulfonic acid (PSSA), PSSNa, PAA, PVA, PSSLi, PSSK, PSSNH4, PSSMg2, PSSAl3, PSSH, chitin, chitosan, cellulose, starch, gum, alginate and carrageenan, polyamide, polyphenol, organic polyester, inorganic polyester and polyanhydride. Polymers include hydrogels. Some benefits of polymers include that they are flexible, stretchable and easy to manufacture, cost-effective or translucent, and can work at low humidity.

[0011] Some polymers have hydrophilic functional groups so they can be water reservoirs. Polymers can also form frameworks to hold salts.

[0012] In other embodiments, the first electrode, the second electrode, and the functional layer are configured in a stacked arrangement.

[0013] The stacked orientation is beneficial because it allows the interface between the layers to have a relatively large surface area in the direction of charge movement between the electrodes. This creates a relatively large surface area for the interface between the layers (e.g., a much larger surface area than the cross-sectional surface area of ​​the layer used in the end-to-end interface connection between the layers). Compared to the smaller contact area, this large surface area of ​​the interface reduces the internal resistance of the wet gas power generation device and provides an opportunity for high current. In principle, in-plane alignment will also work, but ion migration requires a long path, so the internal resistance will be quite high. The large surface area of ​​the interface also allows moisture to penetrate from the first sublayer to a larger surface area in the other sublayers.

[0014] In other embodiments, the sub-layers are arranged in a stacked configuration to form the functional layer.

[0015] In some other embodiments, the first sublayer and the second sublayer are adjacent sublayers within the functional layer.

[0016] The adjacent sublayers provide an electrical interface between the surface of the first sublayer acting as a moisture reservoir and the surface of the second sublayer for movement of charge carriers between the layers. The adjacent sublayers allow moisture to move directly between the layers.

[0017] In some examples, the functional layer is a double-layer structure having two layers, namely, a first sub-layer that acts as a moisture reservoir to the second sub-layer, and a second sub-layer of the functional sub-layer.

[0018] In some other embodiments, when the moisture power generating cell is exposed to moisture, the first sublayer releases charge carriers.

[0019] Advantageously, both the functional sublayer and the first sublayer are MEG layers. This may provide the advantage that in addition to the charge carriers provided by the functional sublayer, additional charge carriers may be provided by the first sublayer to the wet gas power generation device. This increase in the number of charge carriers may improve the electrical performance (such as voltage output) of the device compared to a single layer of MEG.

[0020] In other embodiments, the second sublayer has a net charge opposite to the charge of the charge carriers in the first sublayer.

[0021] The net charge of the second sublayer, which is opposite to the charge of the charge carriers in the first sublayer, facilitates attracting charge carriers from the first sublayer. These charge carriers in the first sublayer can be released. For example, if the second sublayer is a net negative charge (e.g., a GO layer), protons or other positive ions present in the first sublayer (e.g., a polymer) will be attracted toward the second sublayer. This charge attraction can help increase the flow of charge through the MEG device, which can improve the electrical properties of the MEG device. Examples can include increasing the voltage and current of a moisture charging device.

[0022] In other embodiments, the second sublayer includes a carbon-based material.

[0023] In some other embodiments, the second sublayer includes graphene oxide.

[0024] Graphene oxide is known as MEG material. Graphene oxide has a higher density than other more permeable materials such as Mxene. GO can absorb excess water from the polymer layer. GO is negatively charged, so it can attract protons or other positive charge carriers from the polymer layer.

[0025] In other embodiments, the moisture generating device is configured such that the second sublayer is positioned between the first layer and the second electrode, the second layer has a top surface facing the first sublayer and a bottom surface facing the second electrode, and the moisture generating device is configured to prevent moisture from entering the bottom surface of the second sublayer.

[0026] The advantage of preventing moisture from entering the bottom surface of the second sub-layer is that a moisture gradient can be created across the moisture power generation device. This moisture gradient can create a charge gradient within the MEG device.

[0027] In other embodiments, the second electrode is isolated from moisture.

[0028] In some other embodiments, the second sublayer is adjacent to the second electrode and electrically connected to the second electrode.

[0029] In other embodiments, the first sublayer includes an ionic salt.

[0030] The concentration of salts also plays an important role in device performance. The presence of ionic salts in the polymer layer provides mobile ions that can be used as a medium to strengthen the ion concentration gradient across the device. This increases the number of ions within the first (moisture) layer. MEG devices that include ionic salts in the polymer layer can have higher voltage outputs than devices without ionic salts. Such free ions significantly enhance the conductivity of the polymer layer.

[0031] Salts include NaCl and KCl. Li, Na and K are considered Group I alkali metals.

[0032] Ionic salts also help the polymer absorb more moisture. These are hydrophilic salts.

[0033] In other embodiments, the first sublayer includes a hydrogel.

[0034] Hydrogels are three-dimensional networks of polymer chains. Hydrogels are hydrophilic and can absorb large amounts of water. The advantage of using hydrogels is that they have good moisture absorption properties. They can absorb moisture even in low humidity environments. Hydrogels can be hydrated and provide a moisture source to adjacent sublayers. This allows hydrogels to be effectively used as moisture reservoirs (hydration layers). Hydrogels have a three-dimensional framework. This structure provides operational durability because when the hydrogel is hydrated, the structural integrity of the hydrogel layer can be maintained even in a humid environment. This allows the MEG device to maintain performance. Hydrogels are also multifunctional in materials that can be doped with various ions. These are ionic hydrogels. For example, metal ions, salts can be injected into the hydrogel. This provides flexibility in charge carriers when designing MEG devices.

[0035] The hydrogel provides excellent water retention. The hydrogel can contain induced mobile ions. The hydrophilic nature of the hydrogel with efficient moisture absorption means that the device is less restricted by the humidity conditions of the environment than a single layer, conventional MEG, and it can still generate electricity in low humidity environments.

[0036] In other embodiments, the first sublayer is doped with charge carriers.

[0037] The introduction of additional charge carriers enables the electrical performance of wet gas power generation devices to be improved. + The dissociation of ions and moisture also produces abundant H + ions, the main charge carrier is H + ions, the main charge carrier is H + In a lower humidity environment, due to the reduced amount of moisture, less H + The ions are dissociated, but the metal ions from the first sublayer remain mobile and thus the metal ions can contribute to the electrical properties of the MEG device.

[0038] In other embodiments, the device is configured to absorb moisture from the environment, and the electrical performance is improved in higher humidity environments.

[0039] The device may be arranged to absorb moisture from the environment. The design of the device is arranged to allow absorption of moisture from the environment into the device, which is fed into the functional layers to provide the electrical properties of the device.

[0040] According to another aspect, a moisture power generation device includes: a first electrode and a second electrode; a functional layer that releases charge carriers to the first electrode and the second electrode; and a layer that acts as a moisture reservoir to provide moisture to the functional layer.

[0041] In other embodiments, the layer acting as a moisture reservoir to provide moisture to the functional layer is disposed between the first electrode and the second electrode.

[0042] In other embodiments, the functional layer comprises at least two sub-layers, the first sub-layer being the layer acting as a moisture reservoir and the second sub-layer providing charge carriers when provided with moisture.

[0043] According to another aspect, a wet gas power generation device includes: a first electrode and a second electrode; and a functional layer arranged between the first electrode and the second electrode, wherein the functional layer releases charge carriers when the power generation core is exposed to moisture; the functional layer includes at least two sublayers, which are stacked between the first electrode and the second electrode (and adjacent layers are electrically connected); wherein one of the sublayers is a polymer sublayer.

[0044] In other embodiments, when the electricity generating core is exposed to moisture, the polymer sublayer acts as a moisture reservoir to adjacent sublayers.

[0045] According to another aspect, a wet gas power generation device includes: a first electrode and a second electrode; and a functional layer arranged between the first electrode and the second electrode, wherein the functional layer releases charge carriers when the power generation core is exposed to moisture; the functional layer includes at least two sublayers, which are stacked between the first electrode and the second electrode (and adjacent layers are electrically connected); wherein, when the power generation core is exposed to moisture, one of the sublayers that is a polymer sublayer acts as a moisture reservoir to the adjacent sublayer.

[0046] In another aspect, a power cell includes: a first electrode and a second electrode, and a functional layer located between the first electrode and the second electrode, the functional layer releasing charge carriers when the power cell is exposed to moisture.

[0047] In some other embodiments, the functional layer includes at least two sub-layers, the sub-layers are stacked between the first electrode and the second electrode, and adjacent sub-layers are electrically connected.

[0048] When the power generation core is exposed to moisture, each of the sublayers can release charge carriers. Each of the sublayers includes different materials. The first sublayer of the sublayers can be a polymer sublayer. The polymer sublayer can be one of the following: polystyrene sulfonic acid (PSSA), sodium polystyrene sulfonate (PSSNa), polyacrylic acid (PAA), polyvinyl alcohol (PVA), lithium polystyrene sulfonate (PSSLi), potassium polystyrene sulfonate (PSSK), ammonium polystyrene sulfonate (PSSNH4), magnesium polystyrene sulfonate (PSSMg2), aluminum polystyrene sulfonate (PSSAl3), polystyrene thiol (PSSH). The second sublayer of the sublayer includes one of the following: MXene, oxidized MXene, PVA, PAA, GO.

[0049] In other embodiments, a second sublayer of the sublayers is adjacent to the first polymer sublayer.

[0050] In other embodiments, a second one of the sub-layers includes a carbon-based material that releases charge carriers when exposed to moisture.

[0051] In some other embodiments, a first sublayer of the sublayers that is a polymer sublayer is adjacent to the first electrode and electrically connected to the first electrode.

[0052] In other embodiments, the first electrode is permeable to moisture.

[0053] The first electrode may include Ag, Zn, a Zn plate, a Zn foam, Al, Mg, Cu, Ni, Fe, or Ti.

[0054] In some other embodiments, a second sublayer of the sublayers is adjacent to the second electrode and electrically connected to the second electrode.

[0055] In other embodiments, the second electrode is isolated from moisture.

[0056] In other embodiments, the sub-layers have different moisture absorption properties. In other embodiments, the moisture absorption properties of the sub-layers decrease from the sub-layer adjacent to the first electrode to the sub-layer adjacent to the second electrode.

[0057] In other embodiments, when the electricity generating core is exposed to moisture, a first one of the sub-layers that is a polymer layer acts as a moisture reservoir to adjacent sub-layers.

[0058] In other embodiments, the first electrode exhibits an electrochemical reaction when in contact with moisture.

[0059] In other embodiments, the first electrode includes at least one active metal: Al, Cu, Ni, Al, Zn, Zn foam, Mg, Fe or Ti.

[0060] In other embodiments, the functional layer includes PSSNa.

[0061] On the other hand, a power generation core includes: a first electrode and a second electrode, and a functional layer located between the first electrode and the second electrode, when the power generation core is exposed to moisture, the functional layer releases charge carriers; the functional layer includes at least two sublayers, and the sublayers are stacked between the first electrode and the second electrode; when the power generation core is exposed to moisture, each of the sublayers releases charge carriers; wherein the first sublayer of the sublayers is a polymer sublayer and is electrically connected to an adjacent sublayer.

[0062] In other embodiments, the first of the sublayers is PSSNa.

[0063] In other embodiments, one of the sub-layers is electrically connected to the second electrode and comprises GO.

[0064] In another aspect, a power generation cell includes: a first electrode and a second electrode, and a functional layer located between the first electrode and the second electrode, when the power generation cell is exposed to moisture, the functional layer releases charge carriers, wherein the functional layer includes PSSNa. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] In order to understand the present invention more clearly and to put it into practical effect, reference will now be made to a preferred embodiment of the assembly according to the present invention. The following description is given by way of non-limiting example only and with reference to the accompanying drawings, in which:

[0066] Figure 1 A moisture generator cell is shown having a functional layer, a first electrode, and a second electrode.

[0067] Figure 2 A moisture generator cell is shown having a functional layer, a first electrode, and a second electrode.

[0068] Figure 3 An example of acidification of a functional layer of a moisture generator cell is shown.

[0069] Figure 4 (a) shows a schematic illustration of one embodiment of a MEG.

[0070] Figure 4 (b) shows a photograph of the device after acid treatment.

[0071] Figure 4 (c) shows the morphology of GO / PVA before acid treatment.

[0072] Figure 4 (d) shows the morphology of GO / PVA after acid treatment.

[0073] Figure 5 Shown is the voltage output of GO / PVA films acidified by 32 wt % HCl at different relative humidity (RH).

[0074] Figure 6 Shown are the voltage outputs of GO / PVA films treated with different HCl concentrations. Figure 6 (a) shows voltage retention; Figure 6 (b) shows the maximum voltage output. Figure 6 (c) shows the voltage cycle. Figure 6 (d) shows the current cycle.

[0075] Figure 7 (a) shows the XRD patterns of GO film and GO / PVA film.

[0076] Figure 7 (b) is the interlayer spacing of GO film and GO / PVA film.

[0077] Figure 8 (a) is the XPS spectra of GO / PVA films with and without HCl acidification.

[0078] Figure 8 (b) is the ratio of chemical bonds in GO / PVA films with and without HCl acidification.

[0079] Fig. 9(a) Voltage retention of one unit, two units, and four units.

[0080] Fig. 9 (b) is the current cycle of one unit, two units, and four units.

[0081] Fig. 9 (c) The maximum voltage and current for one unit, two units, and four units.

[0082] Fig.10 (a) is a photograph of acidified GO / PVA on carbon cloth and its voltage output at 45% room humidity.

[0083] Fig.10 (b) is the voltage output of flat acidified GO / PVA on RH=75% carbon cloth.

[0084] Fig.10 (c) is the voltage output of acidified GO / PVA wrapped on a glass bottle with a diameter of 2 cm.

[0085] Fig.10 (d) is the voltage output of the acidified GO / PVA wrapped on a glass bottle with a diameter of 1 cm.

[0086] Fig.10 (e) is the pattern design for the device array on FTO glass.

[0087] Fig.10 (f) is a photograph of a working calculator powered by two devices connected in series.

[0088] Fig.11 is an illustration of the device fabrication of: (a) a single MEG cell; (b) four cells in series for voltage measurement; (c) four cells in parallel for current measurement.

[0089] Fig.12 (a) is a photograph of GO film on FTO glass.

[0090] Fig.12 (b) is the voltage cycle of GO film at ΔRH=75%.

[0091] Fig.13 The voltage output of GO / PVA films with different thicknesses after washing with 32% HCl is shown: (a) 6.21 μm. (b) 12.23 μm. (c) 15.53 μm. (d) 23.73 μm.

[0092] Fig.14 The voltage output of membranes with different areas is shown: (a) 0.5 × 0.5 cm 2(b) 1.0×1.0cm 2 (c) 1.5×1.5cm 2 .

[0093] Fig.15 (a) is the FTIR spectra of GO membrane, GO / PVA membrane, and GO / PVA membrane washed with HCl.

[0094] Fig.15 (b) is the Raman spectra of GO film, GO / PVA film, and GO / PVA film washed with HCl.

[0095] Fig.16 The voltage output of GO / PVA membrane washed with (a) 80 wt % acetic acid and (b) 20 wt % sodium hydroxide, and the XPS spectrum of GO / PVA membrane washed with (c) 80 wt % acetic acid and (d) 20 wt % sodium hydroxide.

[0096] Fig.17 (a) illustrates the fabrication of GO / PVA patterns after acidification with 32 wt % HCl.

[0097] Fig.17 (b) illustrates two cells in series for powering a practical device.

[0098] Fig.18 This is an example of the production of an Ag electrode.

[0099] Fig.19 is a digital photograph of the experimental setup, which shows:

[0100] (a) a sample chamber for moisture generation and electrical connection; and

[0101] (b) Keysight system used for electrical output measurement.

[0102] Fig. 20 is an illustration of five cells connected in series for electrical output measurement.

[0103] Fig.21 (a) is the voltage discharge curve of a single MEG battery cell with 1 resistor unit having 2000 kΩ at RH=75%.

[0104] Fig.21 (b) is the voltage retention of 5 connected MEG battery cells at 5.3 hours.

[0105] Fig.21 (c) is the voltage cycle of 5 connected MEG battery cells.

[0106] Fig.21 (d) is the current cycle of 5 connected MEG battery cells.

[0107] Fig. 22 MEG with different functional layers for collecting moisture from the environment is shown: (a) Illustration of abundant and sustainable moisture in the environment. (b) Structural illustration of MEG device. (c) Voltage output of GO membrane at RH=75%. (d) Voltage output of PVA membrane at RH=75%. (e) Voltage output of GO / PVA membrane at RH=75%.

[0108] Fig.23 Comparison of electrical outputs of MEG with different protonations is shown. (a) Voltage hold of MEG acidified with different HCl concentrations at RH=75%. (b) Vmax of MEG acidified with different HCl concentrations at RH=75%. (c) Voltage output of MEG acidified by 32.0% HCl at different RH. (d) EIS of MEG acidified with 32.0% HCl and not acidified with 32.0% HCl at 55% room humidity. (e) Current output of MEG acidified with different HCl concentrations at RH=75%. The Ag electrode area of ​​a single MEG is 0.5×0.2 cm 2 (f) Voltage output cycles of MEG acidified with different HCl concentrations. Moisture was introduced via humid N2 to increase the electrical output until it reached a maximum value and then eliminated via dry N2, as one cycle.

[0109] Fig.24 Characterization and illustration of GO / PVA membranes in acidification are shown. (a) Power generation of GO / PVA membranes after acidification. Protons in the functional groups of GO are mobile by moisture absorption, and charge separation is achieved by proton migration toward the inner layer. In contrast, the migration direction is opposite under moisture removal and facilitates charge recombination. (b) XPS spectra of GO / PVA membranes acidified with HCl and without HCl. (c) Ratio of chemical bonds in GO / PVA membranes acidified with HCl and without HCl. (d) Illustration of functional group changes in HCl acidification. The CO bond is transformed into a C=O bond with better stability after HCl acidification.

[0110] Fig.25 Theoretical determination of the structure and proton binding properties of functionalized graphene oxide using DFT calculations is shown. H binding for O surface functionalized graphene oxide in the absence (a) and presence (b) of carbon vacancies. H binding for OH surface functionalized graphene oxide in the absence (c) and presence (d) of carbon vacancies. HCl acidification promotes the formation of carbon vacancies.

[0111] Fig.26The electrical output of MEG with different units at RH = 75% is shown. (a) Current output of one unit, two units, and four units in parallel. The Ag electrode area of ​​one unit is 0.5 × 0.2 cm 2 (b) Voltage maintenance of one unit, two units, and four units in series. (c) Vmax and maximum current output of one unit, two units, and four units.

[0112] Fig. 27 Demonstration of MEG as a power source in multiple practical applications is shown. (a) Voltage output of acidified GO / PVA films wrapped on glass bottles with different curvatures at RH=75%. (b) Vmax of acidified GO / PVA on carbon cloth before and after 2000 bending cycles. (c) Voltage output of charging a commercial capacitor through MEG at RH=75%. (d) Electrical output of resistors with different resistances connected to MEG at RH=75%. (e) Voltage signal of a pressure sensor powered by MEG at 55% indoor humidity. (f) Photo of a commercial pressure sensor powered by a single MEG at RH=55% indoor humidity. (g) Photo of a working calculator powered by 2 series × 20 parallel MEGs at RH=75%.

[0113] Fig.28 The XRD of the GO membrane in the original state, the GO membrane acidified with HCl and the GO membrane acidified with HNO3 are shown.

[0114] Fig.29 XPS spectra of GO films on FTO glass are shown. (a) GO film in the original state without acidification. (b) GO film acidified by HNO3 vapor. (c) O / C ratio of GO film in the original state and GO film acidified by 70wt% HNO3 solution and vapor.

[0115] Fig.30 The power output of one embodiment of a MEG device is shown.

[0116] Fig.31 The power output of one embodiment of a MEG device is shown.

[0117] Fig.32 The morphology of GO / PVA films is shown. (a) Surface of the film in the original state. (b) Cross-section of the film in the original state. (c) Surface of the film acidified with 32% HCl. (d) Cross-section of the film acidified with 32% HCl.

[0118] Fig.33 A MEG device having a functional layer having two sub-layers is illustrated.

[0119] Fig.34 A MEG device having a functional layer having two sub-layers is illustrated.

[0120] Fig.35 A MEG device having a functional layer having two sub-layers is illustrated.

[0121] Fig.36 A MEG device having a functional layer having two sub-layers is illustrated.

[0122] Fig.36b A MEG device having a functional layer having two sub-layers is illustrated.

[0123] Fig.37 A wet gas power generation device comprising two sub-layers is shown.

[0124] Fig.38 Current characteristics of multiple samples of the power generating core are shown. The performance of the core was measured in different humidity environments (RH%).

[0125] Fig.39 The current characteristics of a plurality of samples of the power generation core are shown.

[0126] Fig.40 The voltage characteristics versus time of a first sample #1 having a silver (Ag) first electrode and a second sample #2 having a Zn plate first electrode are shown.

[0127] Fig.41 The electrical performance of several wet gas power generation devices is shown.

[0128] Fig.42 The voltage of the power generation device with different second sublayers is shown.

[0129] Fig.43 The voltage of a wet gas power generation device with different first sub-layers is shown.

[0130] Fig.44 The voltage across the different sub-layers in a wet gas power generation core is shown for a core including a GO sub-layer and a core including an acidified GO sub-layer.

[0131] Fig.45 The electrical performance of multiple wet gas power generation cells with different top electrodes is shown.

[0132] Fig.46 Voltage results for other samples are shown.

[0133] Fig.47 The voltage of a wet gas power generation device with a single functional layer located between an Ag top electrode and a CNT bottom electrode is shown.

[0134] Fig.48Shown are: a) Schematic of HMEG with different application conditions, b) long-term output performance, and c) self-recovery by absorbing ambient moisture. d) Schematic of HMEG structure. e) Long-term measurement of electrical properties of HMEG at 25°C and 45%±10% RH. f) Radar plot showing overall performance comparison of recently reported MEGs.

[0135] Fig.49 The power generation performance of HMEG is shown. a Voltage output under different RH conditions. b Power generation performance of HMEG under different RH conditions. C Dynamic monitoring of voltage output in response to changing RH. d Power generation performance of HMEG under different working conditions. e Cyclic weight measurement of HMEG with different gel contents exposed to oven (50°C, 15% RH) and ambient conditions (25°C, 45% RH) for 30 minutes. The samples in the original state were dehydrated in an oven (HT) for 30 minutes, followed by water absorption under ambient conditions (RT) to recover water loss. f Weight and current recovery of oven-dried (30 minutes) HMEG after precipitation with different LiCl concentrations under ambient conditions (25°C, 45% RH) for 1 hour. G Voltage retention of HMEG exposed to ambient environment (30%~65% RH) for 4 months. The inset shows the enlarged curve. h V of HMEG under different loads at 45% RH OC and I SC i Comparison of electrical properties of the proposed HMEG with existing MEG.

[0136] Fig.50 Parameters affecting the output performance are shown. a Electrical output of HMEG with different thicknesses of GO layers at 45% RH. b Electrical output of HMEG with different concentrations of LiCl at 45% RH. c EIS measurements of hydrogels with different concentrations of LiCl. d Water absorption capacity of HMEG-0% LiCl, HMEG-1.2% LiCl and HMEG-4.8% LiCl. e Effect of salt concentration on the weight and current output recovery of HMEG. f Raman spectra of hydrogels with (i) 0% LiCl and (ii) 4.8% LiCl. The state of water within the hydrogel was analyzed by tracking the OH peak. 3223cm -1 and 3400cm -1 The peak at 3515cm indicates free water. -1 and 3630cm -1 The peak refers to the intermediate water. g Water absorption capacity of HMEG with different hygroscopic salts at 45% RH. h Electrical properties of HMEG with different hygroscopic salts at 45% RH.

[0137] Fig.51The working principle of HMEG is shown. a FTIR spectra of hydrogels with different concentrations of LiCl. b XRD analysis of hydrogels with and without LiCl. c 2D Raman mapping of hydrogels with different concentrations of LiCl to show the internal water content. D XPS etching analysis of the lower layer GO after peeling from the hydrogel. e Voltage contribution of each component layer at 25°C and 0% RH. f Schematic illustration of the proposed working mechanism under different conditions: (i) ambient conditions, (ii) high humidity (>65%) and (iii) low humidity (<15%). Due to the superior water absorption capacity, the hydrogel begins to collect moisture from the humid air flow. Under dry conditions, water evaporation within the hydrogel is triggered.

[0138] Fig.52 A display of HMEG is shown. a A series of connections of HMEG showing the ability to scale up the voltage output. b The relationship between the voltage output and the number of units, indicating a linear relationship. The inset shows the generated voltage and amplified curves from 168 devices. c Schematic of a flexible HMEG connected in series. d 39 LEDs with a "UNSW" pattern directly powered by 168 devices connected in series. e 100μF and 470μF capacitors are charged with a single core of HMEG and 168 cores of HMEG, respectively. The inset shows the circuit for the charging process. f The current response of a synaptic device driven by a pulse train (amplitude: +3V, width: 10ms, period: 30ms) powered by a charged capacitor. The inset shows a schematic of the synaptic device. g Powered commercial smart window and ink screen: i, iii before connection. ii, iv after connection.

[0139] Fig.53 The fabrication process of hydrogel-based MEG is shown.

[0140] Fig.54 A schematic diagram of the internal structure of the hydrogel is shown.

[0141] Fig.55 Photos of (ac) LiCl powder and (df) PVA-LiCl hydrogel before and after water absorption are shown. (a) LiCl powder before water absorption. (b) Observation of deliquescence of LiCl powder and salt after water absorption at 45% RH for 2 hours. (c) LiCl powder completely deliquesces into liquid after water absorption for 24 hours. (d) PVA-4.8% LiCl hydrogel before water absorption. (e) PVA-4.8% LiCl hydrogel after water absorption for 2 hours at 45% and no physical changes are observed. (f) PVA-4.8% LiCl retains the initial condition after absorption for 24 hours.

[0142] Fig.56Shown are a measurement conditions in an oven (50°C, 15% RH). b Stability of voltage output of HMEG-4.8%LiCl at 50°C and 15% RH.

[0143] Fig.57 The electrical properties of HMEG at 0% RH are shown.

[0144] Fig.58 a Voltage and b current generation performances of devices with unique GO layers at different RH are shown.

[0145] Fig.59 The power generation performance of the device with only GO layer at 0% RH is shown.

[0146] Fig.60 .a Hydrogels left at -20°C for 40 minutes, 2 hours, and 24 hours. The hydrogels retained their original appearance, and no frozen parts were observed after 1 day. b Hydrogels with 0 and 4.8% LiCl left at 50°C for 1 hour. Less shrinkage was observed in the hydrogel with 4.8% LiCl.

[0147] Fig.61 a Voltage performance and b current performance under ambient conditions (25°C, 40% RH) and in an oven (50°C, 15% RH).

[0148] Fig.62 The device without LiCl peeled off the substrate after 1 day under room conditions.

[0149] Fig.63 . Cyclic voltage and weight measurements of HMEG with 4.8% LiCl exposed sequentially to oven (50°C, 15% RH) and ambient conditions (25°C, 45% RH) for 30 minutes.

[0150] Fig.64 .Water retention of HMEG with different concentrations of LiCl.

[0151] Fig.65 .Power output of the device at 45% RH with external resistor connected.

[0152] Fig.66 Long-term voltage stability of devices without a hydrogel layer and b GO layer under room conditions.

[0153] Fig.67 .a, b Effect of hydrogel thickness on the performance of HMEG. c Electrical properties of HMEG with different electrode sizes.

[0154] Fig.68 Water absorption capacity of pure GO layer at 25 °C and 45% RH.

[0155] Fig.69 . Schematic illustration of the interaction between salt ions and water molecules within a low-concentration hydrogel and b high-concentration hydrogel.

[0156] Fig.70 .Change in the amount ratio of intermediate water and free water within the hydrogel after the introduction of LiCl salt.

[0157] Fig.71 Voltage output of HMEG assembled with different top electrodes (a CNT, b Ag, and c Cu) at 45% RH.

[0158] Fig.72 XPS analysis to reveal the resistance of Li and Cl ions across the underlying GO.

[0159] Fig.73 a Cross-sectional SEM image of the peeled GO layer, and b EDS mapping of Cl element. c EDS mapping index.

[0160] Fig.74 a Photograph of the lower GO layer after peeling off the upper hydrogel layer. b Voc and I of the lower GO layer and the original GO at 45% RH SC .

[0161] Fig.75 .CV curves of HMEG under different working conditions.

[0162] Fig.76 .a Photograph of 168 units connected in series and b LED lighting.

[0163] Fig.77 Photographs of 168 cells connected in series in a flat state and b bent state.

[0164] Fig.78 .Schematic diagram of the circuit design of a MEG-powered electronic ink display. DETAILED DESCRIPTION

[0165] Single-layer MEG device:

[0166] In the exemplary device, a functional layer for a wet gas power generation cell is provided. The wet gas power generation device generates electricity due to the interaction of the material with the moisture when exposed to moisture. Ionization occurs when H2O molecules promote the dissociation of functional groups (-OH and -COOH) in the functional layer. The mobile H + ions are released as charge carriers for electricity generation. At least some H + The ions remain mobile to provide the electrical properties of the functional layer.

[0167] Moisture includes H2O molecules. The H2O molecules can be in liquid (water) or water vapor. The term moisture is used in this application and should be understood to refer to H2O molecules in any state.

[0168] The functional layer includes at least one composite layer, wherein the composite layer includes a carbonaceous material and a binder. The carbonaceous material may include a carbon nanomaterial.

[0169] One example of a carbonaceous material is graphene oxide. Graphene oxide (GO) is known to show a high specific surface area, abundant oxygen-containing groups, and good mechanical properties, which exhibits rapid moisture absorption and stable electrical output. Other examples of carbonaceous materials include carbon nanotubes, MXene; or carbon nitride (C3N4).

[0170] When the electrode is applied to the functional layer, the adhesive provides interfacial adhesion between the functional layer and the electrode. The adhesive provides stability of adhesion between the functional layer and the electrode. The functional layer including the adhesive maintains good adhesion to the electrode during, for example, time periods, electrical testing, exposure to moisture. Improved adhesion provides improved mechanical adhesion between the functional layer and the electrode. Improved adhesion can also provide improved electrical stability within multiple charging cycles. Without the adhesive, the functional layer may exhibit poor stability and reliability of electrical properties. For example, the functional layer may become detached from the electrode. The adhesive can be conductive or non-conductive.

[0171] Binders include electrically insulating polymers. Examples of binders include: polyvinyl alcohol (PVA); polyvinyl butyral (PVB); poly(methyl methacrylate) (PMMA); polyvinyl pyrrolidone (PVP). PVA has abundant hydroxyl groups, which allows moisture to be absorbed from the environment. PVA also has good viscosity, which makes it a good candidate for printing. As discussed above with respect to binders, PVA provides stable attachment of the functional layer to the electrode.

[0172] In one device, the functional layer is a composite layer including graphene oxide (GO) and polyvinyl alcohol (PVA). PVA can change the spacing between graphene oxide layers. PVA can increase the spacing between graphene oxide layers. The increase in spacing between layers can increase the maximum voltage and current of a MEG battery cell containing a composite layer of graphene oxide and polyvinyl alcohol.

[0173] Including a binder can increase the interlayer spacing of the carbonaceous material compared to the interlayer spacing of the carbonaceous material without a binder. The increased interlayer spacing allows for greater penetration of moisture into the functional layer. Greater penetration of moisture allows for a greater number of H + Ions can be dissociated. However, if the interlayer spacing increases too much, the internal resistance of the functional layer increases.

[0174] In an exemplary device, a functional layer for a wet gas power generation cell core is provided, wherein the functional layer includes graphene oxide having a ratio of C=O bonds to CC bonds greater than 1:9. Examples of ratios greater than 1:9 include 2:9, 1:8, 1:5, and the like. In some embodiments, the ratio of C=O bonds to CC bonds is greater than 1:8 or greater than 1:7 or greater than 1:6 or greater than 1:5. In some embodiments, the ratio of C=O bonds to CC bonds is less than 1:1. The ratio of bonds in the functional layer can be measured, for example, using X-ray photoelectron spectroscopy (XPS).

[0175] C=O is a double bond between an oxygen atom and a carbon atom. CC is a single bond between a carbon atom and another carbon atom.

[0176] As discussed above, the functional layer can be composed of a carbon-based material and a binder. The carbon-based material can be graphene oxide. The binder can be a polymer binder selected to bond to the conductive substrate. Examples of polymer binders include one or more of the following: PVA, PVB, PMMA or PVP.

[0177] In an embodiment, the graphene oxide and the polymer binder are a substantially homogeneous mixture, wherein the graphene oxide and the polymer binder are mixed in a mass ratio ranging from 100:1 to 2:1.

[0178] In an exemplary device, a functional layer for a moisture power generation core is provided, wherein the functional layer includes treated graphene oxide having an interlayer spacing greater than an interlayer spacing of graphene oxide used to prepare the treated graphene oxide.

[0179] In the functional layer, the treated graphene oxide may have a ratio of C=O bonds to CC bonds greater than 1:9. Examples of ratios greater than 1:9 include 2:9, 1:8, 1:5, and the like. In some embodiments, the ratio of C=O bonds to CC bonds is greater than 1:8 or greater than 1:7 or greater than 1:6 or greater than 1:5. In some devices, the ratio of C=O bonds to CC bonds is less than 1:1. The ratio of bonds in the functional layer may be measured, for example, using X-ray photoelectron spectroscopy (XPS).

[0180] In one illustrative example, the interlayer spacing of the treated graphene oxide is ≥ 0.799 nm.

[0181] As discussed above, the functional layer may be composed of a carbon-based material and a binder. The carbon-based material may be graphene oxide. The binder may be a polymer binder selected to bond to the conductive substrate. Examples of polymer binders include one or more of: PVA, PVB, PMMA, or PVP. The interlayer spacing of the treated graphene oxide may be ≥1.00 nm or ≥1.10 nm.

[0182] In an exemplary device, the functional layer includes a plurality of sublayers, and at least one of the plurality of sublayers has a first ratio of C=O bonds to CC bonds, and at least one of the other sublayers has a second ratio of C=O bonds to CC bonds, and the first ratio is higher than the second ratio. Each sublayer has a different ratio of C=O bonds to CC bonds, and the sublayers are arranged to define a gradient of the ratio in the functional layer.

[0183] In an exemplary device, a moisture power generation cell includes a functional layer, a first electrode, and a second electrode. The functional layer is disposed between the first electrode and the second electrode and is electrically connected to the first electrode and the second electrode. The moisture power generation cell is configured to create a moisture absorption gradient across the functional layer when the moisture power generation cell is exposed to moisture.

[0184] The wet gas power generation cell is charged by the reaction of H2O molecules with the functional layer of the wet gas power generation cell to create ionization. The H2O molecules can be provided in the form of liquid, liquid water or water vapor. The wet gas includes H2O molecules. During ionization, the wet gas is brought into contact with the functional layer and promotes the dissociation of the functional groups (-OH and -COOH) of the functional layer. This releases the mobile H + As charge carriers for electricity generation.

[0185] By creating a charge gradient on both sides of the functional layer, for example, a mobile H + ions, the top side of the functional layer has a high concentration of mobile H + ions, a charge gradient is created across the functional layer. This charge gradient creates a potential difference across the functional layer. + Ions from H + Areas with higher ion concentrations migrate to H + Areas of lower ion concentration, thereby generating an electric current through the functional layer.

[0186] Since when the functional layer is exposed to moisture, the mobile H + Ions are created by the dissociation of functional groups, so by also creating a moisture absorption difference between the two sides of the functional layer, a charge gradient can be created across the functional layer. For example, if the top side of the functional layer is exposed to moisture, a high concentration of H is released at the top layer due to the reaction of the functional layer with moisture. +If the bottom layer of the functional layer is not exposed to moisture, or is exposed to less moisture, a lower concentration of H is released at the bottom layer. + ions. This difference in moisture exposure across the functional layer creates a charge gradient across the functional layer and charges the MEG battery cell.

[0187] The charge gradient across the functional layer is related to the voltage output of the MEG battery cell. Generally speaking, the greater the protonation gradient across the functional layer, the greater the voltage of the MEG battery cell.

[0188] By creating moisture absorption differences on the MEG battery cell, the electrical performance of the MEG battery cell can be improved. In an example embodiment, when the MEG battery cell is exposed to moisture, a moisture absorption difference is created across the functional layer of the MEG battery cell. This moisture absorption difference creates a moisture absorption gradient across the functional layer. When the moisture power generation battery cell is exposed to moisture, the moisture absorption difference creates an ion gradient across the functional layer.

[0189] In an example device, a moisture absorption difference is achieved across the functional layer by providing a first electrode and a second electrode comprising different electrode materials. The electrodes are asymmetric. Preferably the electrodes are asymmetric in moisture absorption properties and thus the electrodes allow different amounts of moisture to penetrate the electrodes and contact the functional layer.

[0190] The first electrode of the MEG device may be permeable to moisture. The second electrode may be impermeable to moisture.

[0191] The first electrode allows moisture to penetrate the electrode and into the functional layer. The second electrode is configured to prevent moisture from penetrating the electrode and into the functional layer. The second electrode can prevent moisture from penetrating the electrode and into the functional layer, and does not allow moisture to pass through the electrode. The second electrode can be waterproof. The second electrode can provide resistance to moisture penetration by preventing at least some of the moisture from penetrating the electrode.

[0192] The first electrode may include silver nanowires or zinc, nickel, magnesium or other metals.

[0193] The second electrode may include at least one of FTO, ITO, carbon nanotubes, graphene, or carbon black and MXene.

[0194] Factors used to control the absorption of moisture into the functional layers of the battery core include the design of the electrodes and the materials used for the electrodes.

[0195] The choice of materials used for the electrodes can affect the electrical performance of the device. When moisture can penetrate one surface of the functional layer more than another surface of the cell, improved performance of the MEG battery device can be created. Because one surface of the functional layer is exposed to more moisture than the other surface and absorbs more moisture, a difference in the absorption of moisture is created across the cell. The difference in moisture in contact with, for example, the top and bottom surfaces creates an electrical potential across the functional layer.

[0196] Reference now Figure 1 , the MEG battery core 100 includes a composite GO / PVA layer 110. This is a functional layer of the MEG battery core. A first electrode 130 is attached to a first surface 120 of the GO / PVA layer 110. A second electrode 150 is attached to a second surface 160 of the GO / PVA layer 110. Figure 1 In the example of , the first surface 120 and the second surface 160 are opposite faces of the composite GO / PVA layer. For the purpose of description, the electrode 130 is referred to as the bottom electrode and the electrode 150 is referred to as the top electrode. Obviously, the orientation of the battery cell is not limiting and these references are used for description purposes only.

[0197] The GO / PVA layer 110 has a length dimension (l) and a depth dimension that are much greater than the thickness dimension (E). For example, the GO / PVA layer has a thickness of about 0.5 mm, a length of about 1 cm, and a depth of about 1 cm. The surface area of ​​the surface 120 and the surface 160 is large compared to the thickness.

[0198] exist Figure 1 In the embodiment of the present invention, the battery cell is configured to promote the absorption of moisture into the top surface 160 of the GO / PVA layer 110 and prevent the absorption of moisture into the bottom surface 120 of the GO / PVA layer 110. When moisture is applied to the battery cell, this configuration helps to create a moisture absorption difference between the surfaces of the functional layers. This promotes abundant moisture to be absorbed into the top surface of the functional layer 160, while no moisture is absorbed into the bottom surface of the functional layer 120.

[0199] exist Figure 1 In the embodiment of the present invention, the electrode 150 is configured to cover only a portion of the top surface 160 of the GO / PVA layer. The electrode does not completely cover the top surface 160. The remaining portion of the top surface of the GO / PVA layer is not covered. This allows moisture to directly contact the top surface. A larger top electrode can produce a larger current carrying capacity through the GO / PVA to the electrode joint. However, if the electrode is too large, water can be prevented from escaping from the GO / PVA layer, and moisture can also be prevented from contacting the surface through the electrode.

[0200] exist Figure 1 In the embodiment, the top electrode 150 is silver.

[0201] In another arrangement, the electrode 150 may cover the entire top surface 160 of the GO / PVA layer. Such an electrode should be a moisture absorber and allow moisture to penetrate the electrode and onto the GO / PVA layer. Such an electrode may be permeable. In one embodiment, the electrode 150 comprises silver nanowires.

[0202] exist Figure 1 In the embodiment of the present invention, the electrode 130 extends over the entire bottom surface of the GO / PVA layer. The electrode 130 covers the bottom surface of the GO / PVA layer. Examples of suitable materials for the first electrode include carbon-based materials, such as carbon nanotubes or graphene. Other suitable materials for the bottom electrode include FTO, ITO, MXene, Au, Pt and carbon black.

[0203] By covering the bottom surface, the electrode 130 reduces the penetration of moisture into the GO / PVA layer 110 through the electrode 130. Preferably the electrode 130 prevents the penetration of moisture into the GO / PVA layer 110. Preferably the electrode has moisture barrier properties to prevent the penetration of moisture into the GO / PVA layer.

[0204] Preferably, the first electrode 130 has a moisture barrier property to prevent moisture from penetrating into the GO / PVA layer 110. By using an electrode having a moisture barrier property, moisture penetration through the first electrode 130 and into the GO / PVA layer is reduced. Preferably, the first electrode 130 prevents moisture from penetrating into the GO / PVA layer 110 through the electrode 130. Figure 1 In the example of , the electrode 130 extends over the entire bottom surface of the GO / PVA layer. Examples of suitable materials for the first electrode include carbon-based materials, such as carbon nanotubes or graphene. Other suitable materials for the bottom electrode include FTO, ITO, MXene, Au, Pt, and carbon black.

[0205] Additional resistance to moisture penetration can be provided by mounting the first electrode 130 on a separate substrate. This can improve the moisture resistance properties of the bottom layer by requiring that any moisture that penetrates the bottom layer 120 of the battery cell must first penetrate the substrate and then penetrate the first electrode 130 to penetrate into the GO / PVA layer.

[0206] exist Figure 1 In the example of FIG. 1 , the electrode 130 covers the surface of the GO / PVA layer 110. Figure 1 As shown in , the first electrode 130 extends over the entire bottom surface of the GO / PVA layer 110. This configuration covers the entire surface to avoid direct contact with moisture. As discussed above, this helps reduce the penetration of moisture over the entire bottom surface of the core.

[0207] The electrical performance of the battery cell is also improved by selecting an electrode material with suitable mechanical properties. Improved electrical performance can be achieved by using an electrode comprising a material having similar mechanical properties to the GO / PVA composite layer (e.g., a material having a thermal expansion coefficient similar to the composite layer). By having similar thermal expansion coefficients, the functional layer composite layer 110 and the electrode 130 tend to expand and contract proportionally. This maintains adhesion between the composite layer 110 and the electrode 130 during use. A small amount of PVA between GO and the electrode also improves the mechanical properties. This helps to extend the use of the MEG battery cell by preventing electrical contact failures and preventing the resistivity of the interface between the electrode and the composite layer from increasing over time.

[0208] exist Figure 1 In some devices, the first electrode is a carbon nanotube. In other devices, the first electrode is graphene having similar mechanical properties to the GO / PVA composite layer.

[0209] In devices where the functional layer is pure graphene oxide, a small amount of PVA or other adhesive can be applied between the functional layer and the electrode to improve adhesion.

[0210] Another benefit of the first electrode 130 extending over the entire surface of the GO / PVA layer 110 is that the contact area between the GO / PVA layer 110 and the electrode 130 is increased compared to an electrode extending partially over the GO / PVA layer. This larger contact area results in an increased surface area of ​​the electrical joint. A larger contact area can reduce the resistivity of the joint.

[0211] Preferably, the bottom electrode 130 includes one or more of the following properties: hygroscopicity, water resistance, moisture resistance, softness, providing good adhesion at the interface with the composite layer, flexibility, light weight, thermal expansion coefficient similar to the composite layer, good adhesion at the GO / carbon nanotube interface, high conductivity, and flexibility.

[0212] The considerations for the top electrode 150 are different from those for the bottom electrode 130. In order to create a moisture gradient across the functional layers of the MEG battery core, absorption of moisture to the top surface 160 of the GO / PVA layer is promoted.

[0213] exist Figure 1In the embodiment of the present invention, the electrode 150 is configured to cover only a portion of the top surface 160 of the GO / PVA layer. The remaining portion of the top surface is uncovered and exposed to allow direct contact of moisture to the top surface when the MEG battery cell is exposed to moisture. The electrode 150 can be permeable. The electrode 150 can be permeable to moisture. A larger top electrode - with a larger contact area with the functional layer - can produce a larger current carrying capacity through the GO / PVA to the electrode joint. However, if the electrode is too large, water can be prevented from escaping from the GO / PVA layer, and moisture can also be prevented from passing through the electrode contact surface.

[0214] Figure 2 Shown in FIG. 1 is another MEG battery cell. Figure 2 Including the above Figure 1 The same GO / PVA functional layer 110 and first electrode configuration 130 as described. Figure 2 In the embodiment, the second electrode 250 is permeable. The second electrode 250 is permeable to allow the penetration of moisture. The second electrode 250 covers the surface of the GO / PVA functional layer 160. In another device, the second electrode may partially cover the surface of the functional layer 160.

[0215] The porosity of the electrode 250 allows moisture to penetrate the electrode and to the top surface of the GO / PVA layer 110. Therefore, a larger electrode can be used that covers a larger portion of the top surface of the GO / PVA functional layer but allows absorption of moisture into the GO / PVA layer. Moisture is absorbed and transferred through the electrode 250 and into the surface of the functional layer 110. The permeable electrode increases the contact area between the electrode 250 and the GO / PVA surface to help achieve higher currents. Figure 2 In the example shown in FIG. 1 , the second electrode 250 covers the top surface of the GO / PVA layer 160 .

[0216] exist Figure 2 In FIG. 2 , electrode 250 is a silver nanowire based electrode.

[0217] More generally, examples of permeable second electrodes include electrodes containing metal nanowires. Preferably, the metal should have good corrosion resistance and a smaller work function than GO. The metal nanowires have a network structure, so moisture can penetrate the electrode and into the GO / PVA layer.

[0218] The top electrode is applied as ink. Preferably, the concentration of the ink includes 0.1 wt% to 20 wt% silver nanowires. In an example embodiment, the ink is a 1 wt% silver nanowire ink. The ink is drop coated or gravure coated or screen coated on the MEG device.

[0219] In an exemplary embodiment, a wet gas power generation cell is provided, wherein the work function of one of the first electrode or the second electrode is higher than the work function of the functional layer, and the work function of the other of the first electrode or the second electrode is lower than the work function of the functional layer to create a work function gradient between the first electrode, the functional layer, and the second electrode.

[0220] The electrical performance of the wet gas power generation core and the choice of electrode materials are also affected by the work function of the material. GO has a work function of about 4.7eV to 4.9eV.

[0221] A suitable electrode configuration can induce a Schottky barrier at the electrode / GO interface, which can be well matched to the diffusion direction of protons in GO, thereby improving the voltage output. In particular, GO has a work function of about 4.7eV to 4.9eV, so a top electrode with a smaller work function will prevent the recombination of electrons and protons. An example of a suitable material is zinc. Zinc has a work function of 4.3, which is much smaller than the work function of GO. In an exemplary embodiment, the top electrode is zinc foil with a thickness of about 0.5mm.

[0222] Preferably, the bottom electrode has a higher work function than the GO / PVA layer. This creates a work function gradient across the MEG battery device from the first electrode to the GO / PVA functional layer to the second electrode.

[0223] The work function gradient can increase from the first electrode to the second electrode, or from the second electrode to the first electrode. Thus, the work function of one electrode is higher than the work function of the GO / PVA layer, and the work function of the other electrode is lower than the work function of the GO / PVA layer. When the work function of one of the first electrode or the second electrode is higher than the work function of the composite layer and the work function of the other of the first electrode or the second electrode is lower than the work function of the composite layer, a work function gradient is created between the first electrode, the composite layer, and the second electrode.

[0224] Preferably, the electrically insulating polymer is water soluble. The GO solution and the binder solution are mixed in a mass ratio of 1:1 by ultrasonic treatment. Other mixing mass ratios from 100:0 to 100:200 can be used. A ratio of 1:1 was found to provide good attachment of GO / PVA to the substrate and electrodes.

[0225] Preferably, the GO and binder solution are in the form of an ink. The ink is printable.

[0226] The following description describes manufacturing techniques and considerations for a wet gas generator battery core. The battery core includes at least one functional layer between two electrodes. The functional layer may include graphene oxide. The functional layer includes a composite layer, the composite layer including a carbonaceous material and a binder. The carbonaceous material may be graphene oxide (GO). The binder may be polyvinyl alcohol (PVA).

[0227] Various configurations of electrodes and substrates are described for different embodiments and manufacturing techniques. A functional layer is deposited onto the electrode substrate so that the bottom surface of the layer is in contact with the electrode substrate. Another electrode is positioned onto the top surface of the layer to complete the battery cell.

[0228] The binder improves the adhesion of the layer to the electrode.

[0229] Other materials can be used instead of GO and / or PVA. Carbon nanotubes are an alternative to GO. Oxygen-containing polymers with tunable electrical properties can be used instead of graphene oxide.

[0230] The functional group density of the MEG battery core can be adjusted to change the electrical properties of the MEG battery core. The functional group density can be adjusted by acid treatment. The acid treatment is described below and includes immersion treatment and steam treatment. The acid treatment can be applied before or after the functional layer is deposited on the electrode. When the functional layer is in liquid form, or when the functional layer is in film form, the functional layer can be applied with acid treatment.

[0231] In an exemplary method, GO powder was synthesized by oxidation of graphite powder according to the Hummers method. A 20 mg / mL GO solution was obtained by dispersing GO powder in distilled water with ultrasonic treatment for 30 minutes. A 20 mg / mL LPVA solution was obtained by dissolving PVA powder (Mw 13000-23000) in distilled water at 90°C for 30 minutes.

[0232] In some samples, fluorine-doped tin oxide (FTO) glass was cut into 2.5 × 2.5 cm 2 and used as substrate / bottom electrode. Other conductive substrates may be used instead of FTO coated glass, such as ITO coated glass or other conductive electrode materials.

[0233] In some other devices, different sized substrates / electrodes were used. In these examples, fluorine-doped tin oxide (FTO) glass was cut into 1.0×2.0 cm 2 sheet and is used as a substrate / bottom electrode.

[0234] The FTO glass was then cleaned with ethanol and deionized water, followed by UV irradiation for 30 min. UV irradiation can remove organic impurities on the substrate.

[0235] By ultrasonic treatment, GO solution and PVA solution were mixed in a mass ratio of 1: 1. Other mixing mass ratios can be used from 100: 0 to 100: 10. 1: 1 can provide good attachment of GO / PVA to the substrate.

[0236] The mixture was directly dried on FTO glass at 50 °C for 12 h to form a 1 × 1 cm 2 GO / PVA film. Further layers of the mixture may be applied to increase the thickness of the GO / PVA layer. Typically, further layers are deposited after the previous layer has dried. In other embodiments, the layers may be different mixtures.

[0237] The mixture can be applied to the substrate using different methods. In one example method, the mixture can be applied using spin coating or drop coating techniques. Printing techniques can also be used to apply the mixture to the substrate, including screen printing. Printing techniques are particularly beneficial when the mixture is an ink.

[0238] The concentration of the material can be controlled. This will affect the porosity.

[0239] In other embodiments, carbon cloth is used as an electrode substrate, which is conductive and flexible. The carbon cloth is soaked in the GO / PVA solution for 10 minutes and dried for 12 hours. Other soaking periods can be used. Different drying periods can be used.

[0240] The top electrode may be applied to the membrane before or after acid treatment of the MEG cell (described below).

[0241] There are several considerations for the electrode configuration that can affect the performance of the MEG cell device, they include the moisture absorption and rejection properties of the electrode, the mechanical properties of the electrode, the work function of the electrode. They are now discussed with respect to each electrode:

[0242] In other systems, a method for preparing a functional layer for a wet gas battery core is provided. The functional layer is provided in the form of a mixture. The mixture is exposed to an acid treatment. The mixture can be a solution of graphene oxide. The mixture can be a mixture of graphene oxide and a polymer binder.

[0243] The acid treatment comprises: applying an acid to the mixture. Preferably, the acid is at least one of hydrochloric acid, nitric acid or sulfuric acid. The acid treatment can be a liquid treatment or a steam treatment.

[0244] Preferably, preparing the mixture comprises: mixing a solution of graphene oxide. The mixture may comprise mixing a solution of graphene oxide with a solution of a polymer binder. Exposing the mixture to an acid treatment comprises: mixing a liquid acid into the mixture. The mixture is a printable solution, and in one embodiment, the acid treatment involves mixing an acid with the printable solution prior to printing the functional layer onto the substrate.

[0245] In other systems, the method includes applying an acid treatment after the mixture is applied to a substrate. The substrate may be an electrode.

[0246] The acid treatment may be applied when the mixture is in liquid form.The acid treatment may be applied when the mixture is in solid form (eg as a functional layer deposited onto an electrode).

[0247] In an example system, the acid used in the acid treatment has a concentration in the range of 0.1 wt% to 70 wt%. The acid used in the acid treatment may have a concentration in the range of 1 wt% to 30 wt% to 50 wt%. The concentration of the acid may be selected based on the acid used in the acid treatment.

[0248] This acid treatment has the effect of increasing the ratio of C═O bonds to CC bonds in the functional layer.

[0249] In an embodiment, the method comprises: preparing a plurality of mixtures. Each mixture comprises graphene oxide and a polymer binder, and then exposing each mixture to a different acid treatment so that each mixture has a different ratio of C=O bonds to CC bonds. Then, stacking the different mixtures to form a functional layer comprising a series of sublayers, and wherein the mixtures are stacked in order of the ratio of C=O bonds to CC bonds. The functional layer comprising a series of sublayers is positioned between a top electrode and a bottom electrode to form a MEG battery cell.

[0250] The step of preparing a mixture of graphene oxide and a polymer binder includes dissolving water-soluble graphene oxide in water to form a graphene oxide solution, dissolving a water-soluble polymer binder in water to form a polymer binder solution, and mixing the graphene oxide solution with the polymer binder solution.

[0251] The graphene oxide solution and the polymer binder solution were mixed in a mass ratio of 1:1.

[0252] The graphene oxide solution may include 10 mg / mL to 30 mg / mL of graphene oxide.

[0253] The graphene oxide solution may include 10 mg / mL to 30 mg / mL of the polymer binder.

[0254] In one example, to treat MEG, the MEG battery cell was immersed in hydrochloric acid for 10 minutes. The MEG battery cell was then washed with distilled water for 10 minutes. The MEG was then dried at 50°C for 12 hours for electrical measurements. Individual samples were immersed in hydrochloric acid with different concentrations, and then the electrical characteristics of each of the samples were tested. Hydrochloric acid with concentrations of 0.5%, 1%, 16%, and 32 wt% was used.

[0255] In this example, the bottom surface of the GO / PVA layer is attached to a conductive substrate. The conductive substrate is liquid-resistant and can therefore prevent acid from penetrating the conductive substrate and onto the bottom surface of the GO / PVA layer. Therefore, it is expected that the bottom surface of the layer is not directly exposed to hydrochloric acid.

[0256] Preferably, the MEG cell is processed before the top electrode is applied to the GO / PVA layer. Thus, the first electrode is applied to the GO / PVA layer and the first electrode and GO / PVA sample are processed. In this example, the sample is processed with only a single electrode attached.

[0257] The benefit of applying the second electrode to the functional layer after applying the acid treatment is that the surface of the functional layer is not covered by the electrode during the treatment. This means that the surface area of ​​the film that will come into contact with the acid is not reduced. Another benefit of applying the second electrode after the acid treatment is that the acid will not damage the second electrode.

[0258] In other systems, the acid treatment is applied after the second electrode has been applied to the functional layer.

[0259] The method comprises the following steps: preparing a GO / PVA mixture; depositing the GO / PVA mixture onto an electrode to form a GO / PVA layer; applying an acid treatment; and applying a second electrode onto the GO / PVA layer.

[0260] As discussed above, in other embodiments, the GO / PVA solution can be mixed with an acid before being applied to the substrate. In this case, the GO / PVA mixture is mixed with an acid. The GO / PVA mixture can be an ink. The solution is then deposited onto a conductive substrate after the acid treatment.

[0261] In other example devices, multiple layers of solutions can be deposited. A first layer is deposited onto a conductive substrate. After the layer is dried, another layer is deposited on top of the first layer. After the other layer is dried, additional layers can be deposited. Depending on the desired electrical properties, each layer can include the same solution or different solutions. For example, the first layer can include a solution that has not been mixed with an acid. Another layer can be deposited onto the first layer, wherein the other layer includes a solution mixed with an acid having a specific concentration (e.g., 1%). Other layers can include solutions mixed with acids of different concentrations. The multiple layers together form a functional layer.

[0262] In an alternative arrangement, an alternative acid treatment technique is used. In this technique, the MEG battery cells are treated by acid vapor. The acid vapor technique can be used in place of the acid leaching technique described above. Different vapor treatments can be used.

[0263] In an example device, a functional layer 310 (e.g., a GO / PVA layer) is suspended above a HCl solution 320, such as Figure 3 . HCl vapor 330 emanates from the HCl solution 320 and contacts the GO / PVA layer 310. The acid vapor is absorbed into the surface of the GO / PVA layer. Various procedures can be used to generate vapor from the HCl solution, for example: a MEG material can be placed on top of the HCl solution and then the container is heated. For example, the HCl solution can be heated from room temperature to 100°C.

[0264] exist Figure 3 In the embodiment, the electrode or substrate is not shown. In other embodiments, the GO / PVA layer is deposited onto the electrode before the acid treatment. The electrode can be a conductive substrate. The electrode can be deposited onto the substrate and the functional layer can be deposited onto the electrode before the acid treatment.

[0265] Preferably, the MEG battery cells and acid are contained in a sealed chamber to prevent HCl vapor from escaping.

[0266] Preferably, the concentration of the HCl solution can be 32 wt%. HCl solutions of different concentrations can be used. For example, 0.5 wt%, 1 wt%, 16 wt%, 32 wt%. Concentrations in the range of 0.5 wt% to 36 wt% can be used. Preferably, the concentration is in the range of 20 wt% to 36 wt%. Most preferably, the concentration is in the range of 30 wt% to 36 wt%.

[0267] In one example treatment, the exposure time is 1 hour. Longer or shorter treatment times may be used to vary the exposure time of the MEG cell to the HCl vapor.

[0268] After exposure to HCl vapor, the MEG battery cell is dried. For example, the battery cell can be placed in an oven for drying.

[0269] Compared to the immersion technique, the benefits of steam treatment include that liquids, especially water molecules from the HCl solution, are less likely to penetrate into the MEG battery cell. Water molecules that penetrate into the battery cell can evaporate during drying and create cracks in the GO / PVA composite layer that damage the battery cell and reduce the electrical performance of the battery cell.

[0270] Other benefits of steam treatment compared to immersing the battery cells in HCl solution include reduced drying time.

[0271] Other acids may be used to treat the functional layer. HNO3 (nitric acid) may be used. Typically, nitric acid is available at between 0.1 wt% and 98 wt%. Sulfuric acid may also be used for the acid treatment. Typically, sulphuric acid is available at between 0.1 wt% and 98 wt%.

[0272] statement:

[0273] In the first system, a functional layer for a wet gas power generation cell core is provided, wherein the functional layer includes graphene oxide having a ratio of C=O bonds to CC bonds greater than 1:9. The atomic ratio of C=O bonds to CC bonds is greater than 1:8 or greater than 1:7 or greater than 1:6 or greater than 1:5. The ratio of C=O bonds to CC bonds may be less than 1:1.

[0274] C=O is a double bond between an oxygen atom and a carbon atom. CC is a single bond between a carbon atom and another carbon atom.

[0275] The functional layer consists of graphene oxide and a polymer binder, which is selected to bond to the conductive substrate. The polymer binder can be one or more of the following: PVA, PVB, PMMA or PVP. The conductive substrate forming the electrode can be mounted on another substrate.

[0276] In the device, the graphene oxide and the polymer binder are a substantially uniform mixture, wherein the graphene oxide and the polymer binder are in a range of 100:1 to 2:1. In the device, the functional layer includes treated graphene oxide, and the treated graphene oxide has an interlayer spacing greater than the interlayer spacing of the graphene oxide used to prepare the treated graphene oxide. In the device, the treated graphene oxide has a ratio of C=O bonds to CC bonds greater than 1:9. The ratio of C=O bonds to CC bonds may be greater than 1:8 or greater than 1:7 or greater than 1:6 or greater than 1:5. The ratio of C=O bonds to CC bonds may be less than 1:1. In the device, the interlayer spacing of the treated graphene oxide is ≥0.799nm.

[0277] The treated graphene oxide may be composed of graphene oxide and a polymer binder selected to be bonded to a conductive substrate. The polymer binder may be one or more of: PVA, PVB, PMMA or PVP.

[0278] The interlayer spacing of the treated graphene oxide may be ≥1.00 nm or ≥1.10 nm.

[0279] The functional layer may include a plurality of sublayers, and at least one of the plurality of sublayers has a first ratio of C=O bonds to CC bonds, and at least one of the other sublayers has a second ratio of C=O bonds to CC bonds, and the first ratio is higher than the second ratio. In some devices, each sublayer has a different ratio of C=O bonds to CC bonds, and the sublayers are arranged to define a gradient of the ratio of C=O bonds to CC bonds in the functional layer.

[0280] In another system, a moisture power generation core includes: (a) a first electrode and a second electrode; and (b) a functional layer according to any one of the other aspects; and wherein the functional layer is disposed between the first electrode and the second electrode and is electrically connected to the first electrode and the second electrode.

[0281] The first electrode may be permeable to moisture and the second electrode may be moisture resistant. The second electrode may include at least one of FTO, ITO, carbon nanotubes, MXene, graphene, carbon black, or a metal. The first electrode may allow moisture to penetrate the first electrode and into the functional layer. The moisture includes H2O molecules. The H2O molecules may be present in liquid water or water vapor. The H2O molecules may be present in both liquid water and water vapor.

[0282] The first electrode may comprise silver or comprise zinc, nickel, aluminum, magnesium or other metals. Preferably, the first electrode may be a silver nanowire. The first electrode may be partially covered silver particles, for example from a silver paste.

[0283] Preferably, the work function of one of the first electrode or the second electrode is higher than the work function of the functional layer, and the work function of the other of the first electrode or the second electrode is lower than the work function of the functional layer to create a work function gradient between the first electrode, the functional layer and the second electrode.

[0284] A method of preparing a functional layer for a wet gas battery core comprises the steps of: (a) preparing a mixture of graphene oxide; and (b) exposing the mixture to an acid treatment.

[0285] In another method, a method of preparing a functional layer for a wet gas battery core includes the steps of: (a) preparing a mixture of graphene oxide and a polymer binder; and (b) exposing the mixture to an acid treatment.

[0286] In the method, the acid treatment comprises: applying at least one of hydrochloric acid, nitric acid or sulfuric acid to the mixture. The acid treatment can be a liquid treatment or a steam treatment. In the method, preparing the mixture comprises: mixing a solution of graphene oxide with a solution of a polymer binder. In the method, exposing the mixture to the acid treatment comprises: mixing a liquid acid into the mixture.

[0287] In the method, the mixture is a printable solution and the acid treatment involves mixing an acid with the printable solution before printing the functional layer onto the substrate. The method may include applying the acid treatment after applying the mixture to the substrate.

[0288] In the method, the acid used in the acid treatment has a concentration in the range of 0.1 wt % to 98 wt %.The acid used in the acid treatment may have a concentration in the range of 1 wt % to 30 wt % to 98 wt %.

[0289] The method may include preparing a plurality of mixtures, each mixture including a carbon-based material and a polymer binder, and then exposing each mixture to a different acid treatment so that each mixture has a different ratio of C=O bonds to CC bonds, and then stacking the different mixtures to form a functional layer including a series of sublayers, and wherein the mixtures are stacked in order of the ratio of C=O bonds to CC bonds. Preferably the carbon-based material is graphene oxide.

[0290] In the method, the step of preparing a mixture of graphene oxide and a polymer binder includes: dissolving water-soluble graphene oxide in water to form a graphene oxide solution, and dissolving a water-soluble polymer binder in water to form a polymer binder solution, and then mixing the graphene oxide solution with the polymer binder solution.

[0291] In the method, the graphene oxide solution and the polymer binder solution are mixed in a mass ratio of 1: 1. The graphene oxide solution may include 10 mg / mL to 30 mg / mL of graphene oxide. The graphene oxide solution includes 10 mg / mL to 30 mg / mL of a polymer binder.

[0292] Some systems provide a moisture power generation cell, comprising: a functional layer; a first electrode; a second electrode; wherein the cell is configured to create a moisture absorption gradient on at least one functional layer when the moisture power generation cell is exposed to moisture. The first electrode and the second electrode may include different electrode materials. The first electrode and the second electrode have different moisture permeability characteristics.

[0293] The first electrode includes at least one of FTO, ITO, carbon nanotubes, mxene, graphene, carbon nanoparticles, or carbon black. The second electrode may include silver nanowires / particles. The second electrode partially extends above the functional layer.

[0294] The first electrode may have moisture barrier properties to prevent moisture from entering the functional layer, and the second electrode is permeable and allows moisture to penetrate the second electrode and into the functional layer.

[0295] The functional layer for the wet gas power generation battery core may include at least one composite layer, the composite layer including a carbonaceous material and a binder. The binder may be water-soluble. The binder may be polyvinyl alcohol (PVA).

[0296] The carbon-containing material may be graphene oxide.

[0297] The adhesive facilitates bonding of the functional layer to at least one electrode. The adhesive may be conductive. The adhesive may be non-conductive.

[0298] The system may provide a moisture generator cell according to any preceding statement, wherein the work function of one of the first electrode or the second electrode is higher than the work function of the composite layer, and the work function of the other of the first electrode or the second electrode is lower than the work function of the composite layer to create a work function gradient between the first electrode, the composite layer, and the second electrode.

[0299] The system may provide an electronic device powered by a moisture generating core comprising a functional layer according to any of the preceding statements. Preferably, the electronic device is configured to have a surface positioned in contact with the skin of a subject in use. Preferably, the electronic device is at least one of a sensor, a memory or a radio transceiver.

[0300] The system may provide a battery pack including a plurality of connected moisture generator cells including a functional layer according to another aspect, the moisture generator cells being stackable.

[0301] According to another aspect, the system provides an electronic device powered by at least one moisture generator battery cell.

[0302] The moisture cell generator is configured to have a surface positioned in close contact with the wearer's skin.The electronic device may include at least one of: a sensor; a memory; and / or a radio transceiver.

[0303] Method A method for manufacturing a wet gas generator cell is provided, comprising the steps of depositing at least one layer of a mixture of a carbonaceous material and a binder onto a substrate, the substrate being a first electrode, drying the layer of the mixture and applying a second electrode so that the layer is positioned between the electrodes.

[0304] The system provides a wet gas generator cell comprising at least one composite layer comprising a carbonaceous material and a binder. Including the binder has the following advantages: It increases the adhesion properties of the layer to a substrate in the cell. This can improve the voltage stability of the cell. The increased adhesion properties can also improve the current stability of the cell. The substrate can be an electrode. The binder can be a water soluble binder. Preferably, the binder is insoluble in acid.

[0305] By varying the amount of carbon nanomaterial and water-soluble binder, the layer thickness can be gradually changed.

[0306] The carbonaceous material may be a carbon nanomaterial. The carbonaceous material may be an organic carbon material. Preferably, the carbonaceous material is graphene oxide (GO). Graphene oxide (GO) shows a high specific surface area, abundant oxygen-containing groups and good mechanical properties, which exhibits rapid moisture absorption and stable electrical output. GO can be modified with oxygen-containing groups or internal structures to further improve its electrical output. This provides adjustable electrical properties. Graphene oxide has the advantage that it is non-toxic.

[0307] Preferably, the binder is polyvinyl alcohol (PVA). PVA has abundant hydroxyl groups, which allows moisture to be absorbed from the environment. Moisture absorbed from the environment absorbs H+ ions, which induces an electric potential. PVA also has good viscosity and also improves the attachment of the film to the substrate. The improved attachment produces a stable battery with a stable electrical output over multiple charging cycles. The battery core provides good voltage retention. PVA can change the spacing between the layers of graphene oxide. PVA can increase the spacing between the layers of graphene oxide. The increase in the spacing between the layers can increase the maximum voltage and current of the battery core.

[0308] Preferably, the layer of carbon nanomaterial and water-soluble binder comprises a solution of carbon nanomaterial and a solution of water-soluble binder mixed in a mass ratio of 1:1. The mixture is an ink. The mixture is stable. The mixture can be solution processed. The mixture is applied to the substrate using different techniques, including printing and coating techniques.

[0309] Preferably, the battery cell comprises a first electrode and a second electrode, and at least one layer of carbon nanomaterial and water-soluble binder is positioned between the first electrode and the second electrode. The electrodes may be deposited using techniques including physical vapor deposition (e.g., sputtering) or solution processing techniques (e.g., printing). The first electrode and the second electrode may be composed of different materials. Preferably, they are conductive materials.

[0310] Preferably, the at least one layer is mounted on a substrate. The substrate may include a first electrode. This allows the layers of the battery core to be applied directly to the bottom electrode. This reduces the size of the battery core. Preferably, the substrate is fluorine doped tin oxide (FTO) glass. Other electrode substrates may be used, including ITO coated glass.

[0311] The substrate is a flexible substrate, such as carbon cloth. The use of a flexible substrate produces a flexible battery core. The flexible battery core provides opportunities for devices that require flexibility (e.g., wearable devices, Internet of Things devices, electronic skin patches).

[0312] The substrate may be stretchable. This may enable the battery cell to be used in stretchable electronic devices.

[0313] Preferably, the second electrode covers a portion of the surface of the layer of carbonaceous material and binder. Preferably, the second electrode does not completely cover the surface of the layer. This allows at least a portion of the layer to be exposed and processable.

[0314] Preferably, the at least one layer has at least one of the following properties: moisture stable; cyclable electrical properties, which allows the battery cell to be charged, discharged and recharged; adhesion to the substrate; adhesion to the electrode; solution processable, such as printing and coating techniques; vapor deposition techniques, such as sputtering.

[0315] Preferably, at least one of the layers of carbonaceous material and binder is treatable to modify the oxygen functional groups in the at least one layer. Modifying the oxygen functional groups may increase the ability of the layer to absorb H. + ions. Preferably, the change in the functional group is an increase in the number of C=O bonds in at least one layer. The increase in the number of C=O bonds can allow H absorbed by at least one layer to + The number of ions increases. This can increase the voltage and / or current produced by the battery cell.

[0316] The layer may be treated before being applied to the substrate. The carbonaceous material and binder are mixed with hydrochloric acid before being applied to the substrate. This may produce a substantially uniform distribution of C=O bonds within the solution of the carbonaceous material and binder. When deposited on the substrate, the layer of carbonaceous material and binder comprises a substantially uniform distribution of C=O bonds.

[0317] Preferably, the at least one layer is formed by depositing a composite of a carbonaceous material and a binder onto a substrate and then drying, wherein the treatment of the layer in order to modify the oxygen-based functional groups in the layer is performed by treating the carbonaceous material and the binder prior to depositing the carbonaceous material and the binder onto the substrate. Preferably, the carbonaceous material and the binder are in the form of ink.

[0318] The layer may be treated after being applied to the substrate. The layer has a first surface and a second surface, wherein the layer is treated on the first surface or the second surface. An advantage of treating one surface of the layer is that the functional groups at the treated surface are changed. This may create a gradient of functional groups on the layer. An increase in the gradient of functional groups can increase the absorption of H + ions. Therefore, when exposed to H + ions, which can increase the potential of the battery cell.

[0319] Preferably, the layer is treated by acidification. Preferably, the layer is treated by hydrochloric acid (HCl) acidification. HCl acidification increases the number of C=O bonds. HCl acidification reduces the resistivity of the layer.

[0320] The battery core may include multiple layers of carbonaceous material and a binder. Each layer may undergo a different treatment. For example, multiple layers may be treated with acids having different concentrations. Different concentrations may produce different amounts of C=O bonds in the layers.

[0321] Preferably, at least one layer is a film. Preferably, the first electrode and the second electrode have different moisture absorption characteristics. Preferably, the layer is applied to the substrate by at least one of the following techniques: spin coating, spray coating, dip coating, drop coating, slot die coating, nanoimprinting, inkjet printing, spray printing, conventional gravure printing, screen printing, flexographic printing, lithographic printing, relief printing, gravure printing and aerosol jetting.

[0322] The viscosity of the mixture is controllable to facilitate different application processes. The concentration of GO can be varied and organic materials (such as PVA) can be added to improve its application characteristics and adhesion on different substrates. The viscosity can also be controlled by adding different amounts of organic materials (such as PVA).

[0323] Preferably, the concentration of hydrochloric acid is between 0.1 wt% and 32 wt%. Preferably, the concentration is 32 wt%. 32 wt% produces good electrical properties for the battery cell. Other concentrations of hydrochloric acid may be used. It has been found that hydrochloric acid with a concentration of 1% produces stable electrical properties over multiple charge and recharge cycles.

[0324] Embodiments have a voltage output and a current output, wherein at least one of the voltage output and the current output is increased after processing the at least one layer.

[0325] The interlayer spacing of the at least one layer is increased by the treatment and increases at least one of the voltage output or the current output of the battery cell. Typically, GO nanosheets exhibit a multilayer structure, and their interlayer spacing can be adjusted to achieve different physical and chemical properties.

[0326] In another system, a wet gas generator battery cell includes at least one layer, the at least one layer including a carbonaceous material, wherein the layer is treated to change the oxygen functional groups in the layer. Changing the oxygen functional groups can increase the release of the layer. + ions. Preferably, the change in the functional group is an increase in the number of C=O bonds in at least one layer. The increase in the number of C=O bonds can allow an increase in the number of H+ ions absorbed by the at least one layer. This can increase the voltage and / or current generated by the battery cell.

[0327] Preferably, the layer is treated after applying the layer to the substrate. Preferably, the at least one layer is formed by depositing a carbonaceous material onto a substrate and then drying, wherein the treatment of the layer to change the oxygen functional groups in the layer is performed by treating the carbonaceous material before depositing the carbonaceous material onto the substrate to form the layer. Preferably, the layer is an ink and the layer is treated by mixing an acid with the ink before depositing the layer onto the substrate. Preferably, the layer comprises a binder.

[0328] In another system, a battery pack includes a plurality of wet gas generator battery core packs according to the first aspect or the second aspect. In an embodiment, the wet gas generator battery cores are stacked. In an embodiment, the wet gas generator battery cores are connected in series. In an embodiment, the wet gas generator battery cores are connected in parallel. An embodiment may include: a plurality of wet gas power generation battery cores including a series electrical connection and a parallel electrical connection between the cores.

[0329] In another system, an electronic device powered by one or more moisture generator battery cells of the first aspect or the second aspect. Preferably, the moisture generator battery cell is configured to have a surface positioned in close contact with the wearer's skin. Preferably, the electronic device further comprises at least one of the following: a sensor; a memory; and / or a wireless communication component / module.

[0330] In another system, a method for making a wet gas generator cell includes the steps of depositing at least one layer of a mixture of a carbonaceous material and a binder onto a substrate, the substrate being an electrode, drying the layer of the mixture and applying another electrode so the layer is positioned between the electrodes. The first electrode may be applied to the substrate.

[0331] Preferably, the second electrode is applied to a portion of the second surface of the layer. Preferably, the second electrode does not completely cover the surface of the layer. This allows at least a portion of the layer to be exposed and processable.

[0332] Preferably, the carbon nanomaterial is graphene oxide (GO). Preferably, the water-soluble binder is polyvinyl alcohol (PVA). Preferably, the solution is a mixed solution of GO and PVA in a mass ratio of 1:1.

[0333] Preferably, the method comprises the further step of treating the layer of carbon nanomaterial and water soluble binder to increase the number of C=O bonds in the at least one layer. Preferably, the layer is treated by acidification. Preferably, the acidification is HCl.

[0334] The method performs the deposition step by at least one of the following techniques: spin coating, spray coating, dip coating, drop coating, slot die coating, nanoimprinting, inkjet printing, spray printing, conventional gravure printing, screen printing, flexographic printing, offset printing, relief printing, gravure printing and aerosol jetting.

[0335] Preferably, the moisture generator cell has a voltage output and a current output, wherein at least one of the voltage output and the current output is increased after processing the at least one layer.

[0336] The method, wherein the first electrode is a material having similar mechanical properties as the composite layer. The method, wherein the first electrode comprises a material having a similar coefficient of thermal expansion as the composite layer. The method, wherein the first electrode comprises carbon nanotubes.

[0337] Preferably, the first electrode comprises at least one of the following properties: waterproof, soft, provides good adhesion at the interface with the composite layer, flexible, lightweight. The structure and expansion coefficient are similar to GO, so the adhesion on GO is good. The resistivity of the connection is thus low to increase the conductivity during operation.

[0338] Preferably, the work function of one of the first electrode or the second electrode is higher than the work function of the composite layer, and the work function of the other of the first electrode or the second electrode is lower than the work function of the composite layer to create a work function gradient between the first electrode, the composite layer and the second electrode.

[0339] The method, wherein the second electrode has a work function lower than the work function of the composite layer. The method, wherein the second electrode has a work function lower than the work function of the composite layer, and the composite layer has a work function lower than the work function of the first electrode.

[0340] The method, wherein the second electrode comprises a permeable material. Preferably, the second electrode comprises a material that allows water to permeate. Preferably, the second electrode comprises silver nanowires.

[0341] The method wherein the second electrode comprises zinc.

[0342] Applications of the wet gas generator battery cell include power supplies for thin film transistors, memory devices (e.g., RRAM, memristors), large area electronics, IoT devices, sensors, wearable devices, and electronic skin patches.

[0343] A moisture generator cell, wherein the first electrode has moisture barrier properties to prevent moisture from entering the layer.

[0344] A moisture generator cell wherein the first electrode prevents ingress of moisture through the first electrode and into the layer.

[0345] A moisture generator cell wherein a first electrode substantially covers a first surface of the layer.

[0346] A wet gas generator battery cell, wherein the first electrode may include a carbon-based conductive material, carbon nanotubes, graphene or carbon black.

[0347] A wet gas generator battery cell, wherein the electrode is a material having similar mechanical properties as the composite layer. A wet gas generator battery cell, wherein the electrode comprises a material having a similar thermal expansion coefficient as the composite layer.

[0348] A moisture generator cell wherein electrodes include carbon nanotubes.

[0349] Preferably, the electrode comprises at least one of the following properties: waterproof, soft, provides good adhesion at the interface with the composite layer, flexible, lightweight. The structure and expansion coefficient are similar to GO, so it adheres well at the GO / carbon nanotube interface. Therefore, the resistivity of the connection is low to increase the conductivity during operation.

[0350] A moisture generator cell, wherein the second electrode is in contact with the second surface or the layer. A moisture generator cell, wherein the second electrode has a work function lower than the work function of the composite layer. A moisture generator cell, wherein the second electrode has a work function lower than the work function of the composite layer, and the composite layer has a work function lower than the work function of the first electrode. A moisture generator cell, wherein the second electrode comprises a permeable material. Preferably, the second electrode comprises a material that allows water to permeate. Preferably, the second electrode comprises silver nanowires.

[0351] A moisture generator cell wherein the second electrode comprises zinc.

[0352] Part 1: Samples and Results

[0353] The following section 1 describes the first series of samples and results:

[0354] Material

[0355] GO powder was synthesized by oxidation of graphite powder according to the Hammers method. A 20 mg / mL GO solution was obtained by dispersing GO powder in distilled water with ultrasonic treatment for 30 minutes. A 20 mg / mL LPVA solution was obtained by dissolving PVA powder (Mw 13000-23000) in distilled water at 90 °C for 30 minutes.

[0356] Preparation of MEG

[0357] FTO glass is cut into 2.5×2.5cm 2and used as substrate / bottom electrode. Other conductive substrates may be used instead of FTO coated glass, such as ITO coated glass or other conductive electrode materials.

[0358] By ultrasonic treatment, GO solution and PVA solution were mixed at a mass ratio of 1: 1. Other mixing mass ratios from 100:0 to 100:10 can be used.

[0359] The mixture was directly dried on FTO glass at 50 °C for 12 h to form a 1 × 1 cm 2 GO / PVA film. Further layers of the mixture may be applied to increase the thickness of the GO / PVA layer. Further layers are typically deposited after the previous layer has dried.

[0360] The remaining exposed area of ​​the FTO glass was covered with insulating tape and spread with Ag paste as the top electrode. Fig.12 Describe this process in more detail.

[0361] In an alternative embodiment, carbon cloth was used as the electrode substrate, being conductive and flexible. The carbon cloth was soaked in the GO / PVA solution for 10 minutes and dried for 12 hours.

[0362] Figure 4 (a) shows a schematic cross-sectional representation illustrating the structure of a MEG battery cell. Figure 4 (b) shows a photo of the MEG battery core after acid treatment. The GO / PVA layer is deposited onto a conductive substrate so that the bottom surface of the GO / PVA layer is in contact with the conductive substrate. In the example described above, the conductive substrate is FTO coated glass. The top electrode is applied to the top surface of the GO / PVA layer. In this example, the top electrode is a silver paste.

[0363] Fig.12 (a) shows the steps for applying the second (top) electrode to the GO / PVA layer of the cell. Fig.12 (a) A top view of a sample showing that a GO / PVA film has been deposited onto a FTO glass substrate and then acidified. Fig.12 In the example of (a), the GO / PVA film partially covers the FTO glass substrate. In other embodiments, the film can completely cover the substrate. In other embodiments, the film can cover other proportions of the substrate.

[0364] Insulation is applied to a portion of the exposed substrate. A top electrode is then deposited onto the top layer of the film. The top electrode is insulated from the bottom electrode to avoid shorting the cell. Fig.12 In the example of , silver (Ag) paste is used for the top electrode.

[0365] The remaining exposed area of ​​the FTO glass was covered with insulating tape and spread with Ag paste as the top electrode. Fig.12 Describe this process in more detail.

[0366] Acid treatment of MEG

[0367] To treat MEG, the MEG battery cell was immersed in hydrochloric acid for 10 minutes. Then, the MEG battery cell was washed with distilled water for 10 minutes. The MEG was then dried at 50°C for 12 hours for electrical measurements. Each sample was immersed in hydrochloric acid with different concentrations, and then the electrical characteristics of each of the samples were tested. Hydrochloric acid with concentrations of 0.5%, 1%, 16%, and 32wt% was used.

[0368] Since the bottom surface of the GO / PVA layer is attached to the conductive substrate, it is expected that the bottom surface of the layer is not directly exposed to hydrochloric acid.

[0369] The advantage of treating the MEG cell before applying the top electrode to the membrane is that the surface area of ​​the membrane attached to the top electrode is protected from acid treatment after the top electrode is applied to the membrane. Meaning: the surface area of ​​the membrane that the acid will contact and change the oxygen groups is reduced. The acid will not contact the portion of the surface connected to the top electrode.

[0370] Electrical testing

[0371] As an example, the top and bottom electrodes of the MEG are connected to a precision source / measurement unit ( Fig. 20 (b)). In this example, a Keysight B2902A measurement unit is used.

[0372] The battery cells were subjected to electrical measurements in environments with different relative humidity (RH). The RH in the sample chamber was controlled using humid N2 and dry N2. For the electrical hold measurement, moisture was input by humid N2 to increase the RH (up to 75% RH) and the electrical output until it reached the highest value and was stopped for the hold measurement. For the measurement of one electrical cycle, moisture was input by humid N2 to increase the RH and the electrical output until it reached the highest value and was eliminated by dry N2 (up to 0% RH) to reduce the RH and the electrical output until it reached the lowest value. The voltage and current output of multiple battery cells were measured by connecting the battery cells in series and in parallel. Figure 5 The results of measurements of voltage retention at 1%, 25% and 55% relative humidity for cells washed in 32% HCl are shown in . This shows that as relative humidity increases, the voltage output by the MEG cell increases.

[0373] Results and discussion

[0374] Figure 4a shows an example of the structure of MEG, which is a relatively simple structure for power generation. Fig.13 Compared with the GO film in a, Figure 4 The device photograph in b shows the uniform surface and good adhesion of GO / PVA film on FTO glass. Fig.13 a shows weak attachment and wrinkles. After HCl acidification ( Figure 4 The morphology of the GO / PVA film with a thickness of 15.53 μm (d) shows a smooth surface and a dense layer structure due to the addition of PVA, which is different from that before acid washing ( Figure 4 The morphology of the GO / PVA film is similar to that of the GO / PVA film of c). The intact and uniform morphology of the GO / PVA film contributes to the stable electrical output in long-term use.

[0375] At different RH ( Figure 5 ) recorded the voltage output of GO / PVA membrane acidified by 32wt% HCl. The maximum voltage of MEG was 0.01V (relative humidity (RH) = 1%), 0.25V (RH = 25%), and 0.61V (RH = 55%), respectively. Therefore, MEG showed almost no voltage output at RH = 1% and increased voltage output at higher RH, which proved that RH is closely related to power generation. Higher RH contributes to more absorbed water and greater H in MEG. + gradient, which results in a higher voltage output.

[0376] The voltage output of the GO / PVA film acidified by HCl solution at different concentrations is shown in Figure 6 b. The maximum voltage increases with thickness (0.74 V, 0.8 V, and 0.85 V for films with thicknesses of 6.21 μm, 12.23 μm, and 15.53 μm, respectively), and shows an insignificant increase for films thicker than 15.53 μm ( Fig.13 The film facilitates water penetration and reduces the H + gradient, which results in a lower voltage output. In addition, with different areas (0.5×0.5cm 2 , 1.0×1.0cm 2 , 1.5×1.5cm 2 ) of the GO / PVA film showed similar maximum voltage values ​​( Fig.14 ), which demonstrates that the voltage is related to the charged ion gradient rather than the membrane area, and that high voltages can be generated with very small areas.

[0377] Voltage retention can be used to evaluate the long-term performance of a device ( Figure 6a). The voltage of the GO / PVA film increases after exposing the film to moisture and shows no significant decrease within 2 hours (RH=75%). These results show better electrical performance in generating a stable and long-lasting voltage output compared to the performance in other GO-based MEGs.

[0378] The maximum voltage of GO / PVA increases with HCl concentration and increases slowly when the HCl concentration is higher than 16%. The maximum voltage of GO / PVA membrane that is not acidified by HCl is about 0.49 V, which is similar to that of GO membrane that is not acidified by HCl ( Figure 6 b) are almost the same. The maximum voltage of the GO / PVA membrane acidified with 32% HCl is 0.85 V, which is much higher than the maximum voltage (0.49 V) of the membrane that has not been acidified by HCl. Therefore, the voltage output of the acidified GO / PVA membrane is closely related to the HCl concentration. HCl acidification can be adopted as an easy and effective method to greatly improve the voltage output of the GO / PVA membrane.

[0379] Voltage cycling of the GO / PVA membranes was also studied to evaluate the stability of MEG ( Figure 6 c). GO membrane ( Fig.12 The voltage cycle of b) is not as stable as that of GO / PVA film, because PVA can provide a stable structure and good attachment of the film to the substrate. The GO / PVA film shows similar voltage output and the same maximum voltage output in each cycle, which proves that the GO / PVA film can generate a stable voltage output.

[0380] Figure 6 d shows the short-circuit current (I sc ), the short-circuit current increases with the concentration of HCl (for membranes acidified with 32%, 16%, 1%, 0.5%, and 0% HCl, the corresponding I sc =9.28 μA, 8.32 μA, 6.05 μA, 3.51 μA and 19.71 nA). The maximum current of the GO / PVA film acidified with 32% HCl is about 9.28 μA and is significantly higher than the maximum current (19.71 nA) of the film not acidified with HCl, which is due to the introduction of H in the HCl acidification. + The resistance decreases after that. The GO / PVA film should be non-conductive because a large number of functional groups are attached to the carbon plane. However, the resistivity of the GO / PVA film after acidification with 32% HCl decreases to 0.9 MΩ-1.2 MΩ, which is beneficial to improve the electrical performance.

[0381] The diffraction peaks of GO / PVA film showed lower angles than that of GO film and shifted to higher angles after increasing HCl concentration ( Figure 7a). The interlayer spacing of the GO / PVA film can be calculated using the diffraction angle ( Figure 7 b).

[0382] Compared with the GO film, the GO / PVA film showed a higher interlayer spacing, where the spacing was 0.77 nm for the GO film, 1.26 nm for the GO / PVA film, 1.19 nm for the GO / PVA (1% HCl) film, and 1.10 nm for the GO / PVA (32% HCl) film. The polymer molecules of PVA can enter the interlayer of GO, where the carboxyl groups from GO can react with the hydroxyl groups in the crosslinking. The crosslinking between GO and PVA bridges the adjacent GO sheets and expands the interlayer spacing, which may explain: compared with the GO film, the GO / PVA film shows a higher interlayer spacing.

[0383] In addition, the spacing of the GO / PVA film was reduced after HCl acidification. The shortened spacing of the GO / PVA film acidified with HCl can be attributed to the charged ions (H + ) is caused by H + can be absorbed by oxygen-containing groups and inhibit the cross-linking of GO and PVA. The FTIR spectra of GO / PVA film and GO / PVA (32% HCl) film are almost the same as that of GO film ( Fig.15 a). Due to the addition of PVA, the Raman spectra of GO / PVA film and GO / PVA (32% HCl) film are flatter than that of GO film ( Fig.15 b), which proves that PVA was not washed away by distilled water or HCl in our work.

[0384] Oxygen functional groups are closely related to moisture absorption and power generation, which can be characterized by the C1s region in XPS. In order to study the effect of HCl acidification on the modification of functional groups for increasing voltage output, Figure 8The GO / PVA membranes acidified with HCl and the GO / PVA membranes not acidified with HCl were analyzed in the figure. The C1s peaks in GO / PVA (0% HCl) with binding energies of 284.8 eV, 286.2 eV, 287.0 eV, and 289.2 eV represent CC (45.29 at.%), CO (19.18 at.%), C=O (4.67 at.%), and OC=O (4.84 at.%). The C1s peaks in GO / PVA (32% HCl) with binding energies of 284.8 eV, 285.9 eV, 287.0 eV, and 289.0 eV represent CC (28.30 at.%), CO (14.26 at.%), C=O (20.75 at.%), and OC=O (4.49 at.%). Therefore, the ratio of CO bonds decreased after HCl acidification, while the ratio of C=O bonds increased after HCl acidification. After 32% HCl acidification, the C / O ratio in the GO / PVA film decreased from 2.96 to 2.12, which proves that acid oxidation occurred in the acid washing. In HCl acidification, the epoxy groups can be arranged in a row, which leads to the cleavage of the CC bonds. The epoxy chains tend to be oxidized to epoxy pairs and converted to carbonyl pairs because the carbonyl groups are more stable under this condition. C=O with stronger polarity attracts H + The higher voltage output can be attributed to the more C=O bonds, which can attract more H + For potential generation.

[0385] Also in Fig.16 c and Fig.16 d, oxygen-containing groups in GO / PVA membranes washed with acetic acid and NaOH were studied. The GO / PVA membrane washed with acetic acid showed CC (35.96 at.%), CO (22.28 at.%), C=O (1.27 at.%), OC=O (6.13 at.%), while the GO / PVA membrane washed with NaOH showed CC (37.86 at.%), CO (25.24 at.%), C=O (2.74 at.%), OC=O (2.47 at.%). The maximum voltages of the GO / PVA membranes washed with acetic acid and NaOH were 0.34 V and 0.22 V, respectively, which were relatively lower than the maximum voltages of the membranes acidified with HCl because the ratio of C=O in the GO / PVA membranes washed with acetic acid and NaOH was lower. Therefore, the ratio of C=O is related to the voltage output of the GO / PVA membrane. Furthermore, the higher C / O ratio in the acidified films contributes to the lower resistivity of the GO / PVA films, which significantly improves the current output (19.71 nA to 9.28 μA for one cell after acidification). In addition, the peaks of CO and OC═O slightly shift to lower binding energies after HCl acidification.

[0386] GO / PVA MEG battery cells can be directly connected in series or parallel to increase voltage or current output. Fig.11 (b) and Fig.11 (c) is a schematic diagram showing four battery cells connected in series for voltage measurement and four battery cells connected in parallel for current measurement, respectively.

[0387] The voltage of two and four cells in series showed good retention without significant drop over 2 hours ( Fig. 9 a). For one cell, two cells, and four cells, the maximum cell voltages are 0.85V, 1.70V, and 3.38V, respectively. Fig. 9 c). Parallel units also show that as more units are involved, the current output increases ( Fig. 9 b). The maximum current of the cells is 9.28, 18.16, and 40.69 for one cell, two cells, and four cells, respectively. Therefore, the voltage and current of the MEG battery cell increase linearly with the output of one cell, which demonstrates the potential application in generating high electrical output by simple assembly of cells (battery cells).

[0388] GO / PVA films acidified with 32% HCl were also fabricated on carbon cloth for flexible device applications. 2 ) can reach a voltage of 0.506V( Fig.10 b).

[0389] GO / PVA films were attached to glass bottles with different radii to study the effect of film curvature on the voltage output of GO / PVA films. The voltage of films with different curvatures increased to a maximum value within 150s-300s. For films with 0cm -1 、0.5cm -1 and 1.0cm -1 The maximum voltages of the films with curvatures of 0.83V, 0.85V and 0.84V are respectively Fig.10 b- Fig.10 d). Therefore, the voltage output through the acidified GO / PVA film on carbon cloth shows a stable voltage output on surfaces with different curvatures, which demonstrates great potential in the preparation of flexible devices.

[0390] Furthermore, by dividing the membrane into small pieces to provide practical devices, device arrays can be easily realized ( Fig.10 e). First, the acidified GO / PVA film was fabricated on FTO glass by the above method, followed by dividing the film into 20 cores connected in parallel and spreading Ag paste as the top electrode ( Fig.17a). A unit with 20 cores in parallel can be connected in series with other units to improve the electrical output ( Fig.17 b). The array (2 in series × 20 in parallel) can provide enough power to power a calculator ( Fig.10 f)

[0391] In another example, five battery cells are connected in series to test the electrical output. Figures 18 to 21 Describe the example.

[0392] For a single core, a mixed solution of GO and PVA (mass ratio = 1:1) was dried on FTO glass at 50 °C for 12 h to form a GO / PVA film (thickness ≈ 15 μm; area ≈ 1 × 1 cm 2 ), followed by acidification with 32% HCl (the membrane was immersed in HCl solution for 10 minutes). Then, it was washed with distilled water for 10 minutes and dried at 50°C for 5 hours. The silver paste was spread on the membrane (area ≈ 0.1 × 0.5 cm 2 ) to make a silver top electrode, and the top electrode was dried at 50°C for 10 minutes ( Fig.18 (b)).

[0393] The relative humidity (RH) in the sample chamber is controlled by the input of humid N2 and dry N2 ( Fig.19 a). The electrical output was recorded in a Keysight B2902A Precision Source / Measurement Unit ( Fig.19 b) The connection of five cores in series is illustrated in Fig. 20 For the hold measurement, humidity was input by humid N2 to increase RH (up to 75% RH) and electrical output until they reached the highest value, and then stopped for the hold measurement. To measure the voltage / current cycle, humidity was input by humid N2 to increase RH and electrical output until they reached the highest value. Then, the humidity was eliminated by dry N2 (up to 0% RH) to reduce RH and electrical output until they reached the lowest value.

[0394] Complete experimental results and data tables

[0395] Table 1: Details of experimental results and data

[0396]

[0397] For the humidity cycling experiment, calculation of the average time for the voltage of the 5 cores in series to recover to 80% of its peak value when the humidity level was reintroduced. The average time for the 5 cores to return to 80% of the peak value was 17.75 seconds.

[0398] based on Fig.21a, Voltage discharge curve of a single MEG cell produced by connecting it to a (2000 k ohm) resistive load at RH = 75%. The discharge of the MEG cell was observed to be over 7000 seconds. The voltage retention of the 5 connected MEG cells was measured over 5.3 hours, and the voltage output was stable at Fig.21 b shows >4.1 V after 5.3 hours. Fig.21 c and Fig.21 In d, voltage cycling and current cycling were tested on 5 connected MEG cells, with the voltage peak recovering above 4 V and the current peak at ∼58 μA.

[0399] in conclusion

[0400] Herein, MEG battery cells have been fabricated from GPVA films treated with HCl, which can respond to moisture and generate electricity without any other stimulus. By adding PVA, GO / PVA films show better attachment to the substrate and more stable electrical output. At RH=75%, the voltage increased from 0.49V to 0.85V and the current increased from 9.28nA to 19.71μA after 32% HCl acidification, which provides an easy way to significantly improve the electrical performance. The voltage can be maintained for more than 2 hours without a significant decrease, which proves its stable electrical output for long-term applications. By a simple assembly of 5 MEG battery cell units connected in series or in parallel, a voltage of about 4.1V or a current of 58μA (peak) is easily generated, which shows great potential in powering commercial devices. In addition, GO / PVA films have also been fabricated on soft and flexible carbon cloth, and a voltage higher than 0.8V was generated within 2 hours, which proves its suitability for the fabrication of flexible devices.

[0401] This paper presents acidified membranes of GO and polyvinyl alcohol (PVA) for MEG battery cells. PVA, which has abundant hydroxyl groups and good viscosity, can not only absorb moisture from the environment, but also improve the attachment of the membrane to the substrate, which leads to stable electrical output. In addition, due to the optimization of functional groups after acidification, the voltage and current output of the GO / PVA membrane are greatly improved, which provides an easy way to prepare MEG with high and stable electrical output. A single MEG battery cell unit can produce a high voltage of 0.85V and a significant current of 9.28μA at 75% relative humidity. The MEG battery cell shows voltage retention for more than 2 hours without obvious voltage reduction. MEG battery cells can also be connected in series and / or in parallel to further increase their electrical output. The voltage of five MEG battery cells in series reaches up to 4.1V, which is high enough to power some practical electrical devices. Therefore, this MEG battery cell provides a feasible method for designing energy collection from abundant moisture in terms of powering practical devices.

[0402] Due to the huge demand for power supply, energy harvesting from moisture has received increasing attention in practical applications due to its abundant source. In this paper, the electrical properties of GO / PVA films, which were prepared by drop coating and then HCl acidification to improve their electrical output, were studied. GO / PVA films acidified with 32% HCl can generate an excellent voltage of 0.85V and a high current of 9.28μA at 75% relative humidity, which can be further improved by simple assembly (4.1V or 58μA (peak) for five units in series or parallel). Electrical output was also achieved on flexible carbon cloth, which presents an easy and effective method to generate enhanced electrical properties for energy supply for flexible electronic devices.

[0403] The various embodiments of the battery cells described above provide self-charging batteries that provide high current output and voltage output in humid environments. Such battery cells have applications in many electronic devices. In particular, the high current output and voltage output and stable output of the MEG battery cells make the embodiments a suitable power source for many wearable technologies that allow the battery cells to be positioned in high humidity environments, such as in contact with human skin, which has approximately 80% to 100% humidity. These high humidity environments provide H + ions to maintain the charge on the battery cell. Suitable applications include health wearables, including various body sensors and electronic skin patches. The voltage and current levels generated by the MEG battery cell enable powering of Internet of Things (IoT) devices, which may include sensors and / or wireless communication modules, such as Bluetooth radio transceivers.

[0404] Part 2: Samples and Results

[0405] The following section 2 describes the second series of samples and results:

[0406] Acidified GO membranes containing a small amount of polyvinyl alcohol (PVA) were used for MEG applications. PVA with hydroxyl groups and good viscosity not only absorbs moisture from the environment but also improves the attachment of the membrane to the substrate, which leads to a stable device structure and stable electrical output. Most importantly, the electrical output of the GO / PVA membrane is greatly improved due to the optimization of functional groups and the reduction of membrane resistance after acidification, which provides a facile way to manufacture MEG with high and stable electrical output. A single unit can generate a high voltage of 0.85 V and 9.28 μA (92.8 μA·cm 2 ) of the significant current, the voltage and current in MEG 6,12Among the highest reported electrical outputs of GO. Within 2 hours, MEG showed good voltage maintenance without obvious drop. MEG can also be connected in series or parallel to further improve its electrical output. The voltage and current of four MEG units reached up to 3.38V and 40.49μA, respectively, which are high enough to power some practical electronic devices. Therefore, this paper provides a feasible method to modify functional groups in GO and produce improved electrical output for powering practical electronic devices.

[0407] Method for samples of part 2

[0408] Material

[0409] Hydrochloric acid (HCl), acetic acid, sodium hydroxide (NaOH), polyvinyl alcohol (PVA) powder (Mw 13000-23000), silver paste and silver nitrate were purchased from Sigma. GO powder was prepared according to the Hammers method. 33 Synthesized by oxidation of graphite powder. 20 mg / mL GO dispersion was obtained by dispersing GO powder in distilled water with ultrasonic treatment for 30 minutes. 20 mg / mL PVA solution was obtained by dissolving PVA powder in distilled water and stirring at 90 °C for 30 minutes.

[0410] Manufacturing of MEG

[0411] Fluorine-doped tin oxide (FTO) glass was cut into 1.0×2.0 cm 2 The FTO glass was then cleaned with ethanol and deionized water, followed by UV irradiation for 30 minutes. The GO dispersion and PVA solution were mixed at a mass ratio of 1:1 (maximum ratio to achieve good attachment of GO / PVA film to the substrate) by ultrasonic treatment for 30 minutes, and then dried directly on the FTO glass for 12 hours to form a 1.0×1.0 cm 2 GO / PVA film. The edges of the GO / PVA film were covered by insulating tape to avoid short circuits, and Ag paste was printed onto the film as the top electrode. For the film made on carbon cloth (substrate / bottom electrode), the carbon cloth was soaked in the above GO / PVA dispersion for 30 minutes and then dried at 50°C for 12 hours.

[0412] Chemical treatment of MEG

[0413] For MEG acidification, MEG was immersed in HCl solutions with different concentrations for 10 minutes. MEG was then washed with distilled water until no chloride ions were detected by silver nitrate solution. MEG was then dried at 50°C for 24 hours for electrical measurements and powering electrical devices. For MEG washed with other reagents, MEG was immersed in acetic acid or NaOH solution for 10 minutes, and then washed with distilled water until pH = 7.

[0414] Electrical Measurement

[0415] The electrodes of the MEG are directly connected to a Keysight B2902A precision source / measurement unit for electrical output measurement. Humid N2 and dry N2 are used to control the RH in the sample chamber. Compressed N2 is used as dry N2 to reduce the RH in the sample chamber. Humid N2 is obtained by passing dry N2 through deionized water to increase the RH in the sample chamber. For electrical output holding measurement, moisture is input by humid N2 to increase RH and electrical output until the electrical measurement is finished. For electrical output cycle measurement, moisture is input by humid N2 to increase RH and electrical output until it reaches a maximum value, and then it is eliminated by dry N2 to reduce RH and electrical output. The voltage and current outputs of multiple cells are measured by connecting the cells in series and in parallel, respectively.

[0416] Electrical output of MEG

[0417] Moisture from water evaporation is an abundant and sustainable resource on Earth ( Fig. 22 a), which can be collected by MEG and included into a self-powered system. Fig. 22 b shows the schematic structure of MEG, in which carbon-based materials are used as functional layers, and silver paste and fluorine-doped tin oxide (FTO) glass are used as top and bottom electrodes, respectively. Moisture from the environment is absorbed by the hydrophilic functional layer and promotes charge separation between the top electrode / bottom electrode to achieve power generation. In order to optimize the functional layer, three types of materials (GO, PVA, and GO / PVA) were used to fabricate the device, and the device was tested at RH = 75%. Fig. 22 c- Fig. 22 As shown in e, for GO, PVA and GO / PVA, the maximum voltage (V max ) outputs are 0.48 V, 0.26 mV, and 0.50 V, respectively. Obviously, the GO membrane outperforms the PVA membrane in generating high voltage output, but significant fluctuations in voltage are observed ( Fig. 22 c). During the electrical measurements, the GO film was unable to attach tightly to the FTO glass due to poor interfacial adhesion, which reduced the stability and reproducibility of the voltage output. Differently, GO / PVA exhibited high and stable voltage output because PVA can act as an adhesive to greatly improve the interfacial adhesion ( Fig. 22 e). Therefore, GO / PVA was selected as the functional layer to fabricate MEG with high and stable electrical output.

[0418] The proton concentration gradient across the functional layer is crucial for proton migration and thus dominates the voltage output. In general, higher concentration gradients can generate higher voltages, which can be obtained from higher RH and enhanced protonation ability of the functional layer. Gao et al. reported that the number of surface protons increased during acidification, thus leading to paper-based MEG 13 Here, GO / PVA films were treated with hydrochloric acid (HCl) solutions having different concentrations including 32.0%, 16.0%, 1.0%, 0.5% and 0.0% to adjust the functional group density. Fig.23 a- Fig.23 The corresponding V of GO / PVA film is shown in b. max The V of the device treated with 32.0% HCl was 0.85 V, 0.82 V, 0.69 V, 0.61 V, and 0.50 V, respectively, which showed good retention within 2 hours. max is 0.85V, which is among the highest reported voltages for single MEG. Obviously, acidification can greatly improve the voltage output because it can enhance the protonation capacity, resulting in a larger protonation gradient. The electrical output of MEG acidified by 32.0% HCl under external scanning voltage was studied. The current output of MEG under positive external voltage is significantly higher than that of MEG under negative external voltage. It is caused by the difference in MEG resistance, which is 0.02MΩ-26MΩ under positive external voltage and 0.35MΩ-2.19MΩ under negative external voltage. It is proved that the acidified GO / PVA membrane generates a huge protonation gradient between the top and bottom surfaces. After soaking the membranes (acidified by 0.0% and 32.0% HCl, respectively) in 1mL distilled water for 10 minutes, the pH of the water soaking different membranes showed the same value. Therefore, it is the dissociation of functional groups, rather than the ionization of H from the HCl solution. + , resulting in a protonation gradient.

[0419] To exclude other variables, the surface morphology was characterized using scanning electron microscopy (SEM) on GO / PVA films acidified with 0.0% and 32.0% HCl. Fig.32 The morphology of the two films did not show significant changes. At the same time, the cross-sectional SEM images showed that the film microstructure and thickness remained unchanged. In addition, in the case of films with different film areas (e.g., 0.5×0.5 cm 2 , 1.0×1.0cm 2 and 1.5×1.5cm 2) device, showing that the voltage remained approximately the same. In addition, the V max is 0.49 V, which is much lower than the V of the GO / PVA film acidified by 32.0% HCl. max Therefore, it is the acidified GO rather than the acidified PVA that contributes to the high voltage output (V max =0.85 V). Therefore, these results exclude the effects of membrane morphology, membrane area, and PVA on the high voltage output of the acidified GO / PVA membrane.

[0420] To further confirm the proton concentration-induced potential across the membrane, different RHs of 1%, 25%, 55%, and 75% were performed on the top surface of the device. Fig.23 As shown in c, the corresponding V max are 0.02 V, 0.22 V, 0.60 V and 0.85 V respectively. In addition, the V max are 0.85V and 0.02V respectively. Due to the negligible protonation gradient between the two top sides of the GO / PVA membrane, the MEG with two top electrodes shows almost no voltage output. Therefore, the protonation gradient is closely related to the voltage output of MEG. In addition, this paper studies the effect of membrane thickness on the voltage output of GO / PVA membrane acidified by 32.0% HCl. GO / PVA membranes with different thicknesses of 23.73μm, 15.33μm, 12.23μm and 6.21μm can produce 0.85V, 0.85V, 0.80V and 0.75V, respectively. MEG with thinner GO / PVA membranes facilitates the migration of water toward the inner layer and leads to a lower gradient of absorbed water between the top and bottom sides, which reduces the protonation gradient and voltage output. The above results clearly indicate that RH and functional group density in the GO / PVA device jointly determine the protonation gradient and voltage output.

[0421] It should be noted that RH is usually an uncontrollable condition for MEG to generate high voltage in practical applications. Therefore, optimizing the functional group density of the functional layer is particularly important to obtain desirable voltage and current output. Fig.23 As shown in a, HCl treatment can adjust the density of functional groups, thereby generating various voltage outputs. At the same time, cycle stability is another key parameter that determines the performance of MEG. Moisture is carried to the top surface of the device by N2 gas to generate electrical output. When moisture is extracted by dry N2, the electrical output drops sharply. Electrochemical impedance spectroscopy (EIS) of GO / PVA acidified with and without HCl was performed in room humidity to analyze the conductivity of different MEGs ( Fig.23d). Compared with GO / PVA not acidified with HCl, GO / PVA acidified with HCl showed much lower resistance, which was caused by more mobile ions in the acidified GO / PVA and was beneficial to achieve high current output. Specifically, after 32.0% HCl acidification, the maximum current output of MEG increased from 19.71 nA (197.1 nA·cm 2 ) increased to 9.28μA (92.8μA·cm 2 ), which showed a significant improvement due to acidification ( Fig.23 e). Fig.23 f shows the cyclic voltage output of MEG acidified with different HCl concentrations. Obviously, as the HCl concentration increases, the device produces a gradually increasing voltage and exhibits excellent cycling stability without obvious degradation in each cycle, which also shows great potential in the application of humidity sensors. The electrical outputs of recently reported MEGs are summarized in Table 1. Obviously, compared with the reported MEG, the MEG with acidified GO / PVA in this work exhibits a more comprehensive electrical output.

[0422] Table 2 Summary and comparison of MEG

[0423]

[0424] Working mechanism

[0425] exist Fig.24 a Illustrate the proposed power generation mechanism of acidified GO / PVA MEG, which includes ionization, charge separation and charge recombination. 18 The protons in the functional groups are immobile without the absorption of water from moisture. During ionization, moisture on the top side of the GO / PVA membrane promotes the dissociation of the functional groups (-OH and -COOH), which releases the mobile H + As charge carriers for power generation. Then, because of the mobile H + The concentration is high, so H + Migrate from the top side to the bottom side, which enables charge separation and voltage generation. After moisture removal, the mobile H + Migrate along the direction of water migration towards the top side and cause charge recombination 11 Therefore, the charging and discharging process is triggered directly by moisture rather than by complex chemical reactions, so that MEG can be quickly charged and exhibit stable electrical output by harvesting this clean energy.

[0426] To verify the improved MEG device performance caused by the increase in group density after HCl treatment, material characterizations such as X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were analyzed on acidified and non-acidified films. The diffraction peaks of the GO / PVA film showed a lower diffraction angle (14.4° to 6.6°) than that of the GO film, and shifted to a higher diffraction angle (6.6° to 8.0°) after increasing the HCl concentration. The interlayer spacing of the GO / PVA film can be calculated by Bragg's law. The GO / PVA film shows a larger interlayer spacing than the GO film, wherein the interlayer spacing is 0.77nm for the GO film, 1.26nm for the GO / PVA film (0.0% HCl), 1.19nm for the GO / PVA film (1.0% HCl), and 1.10nm for the GO / PVA film (32.0% HCl). The polymer molecules of PVA can enter the GO interlayers and expand the interlayer spacing, which can explain the larger interlayer spacing shown in the GO / PVA film than in the GO film. The cross-links between GO and PVA bridge the adjacent GO sheets because the carboxyl groups from GO can cross-link with 23 The hydroxyl groups in the GO / PVA film react with each other, which helps to form a more uniform and stable structure. In addition, after HCl acidification, the interlayer spacing of the GO / PVA film is reduced. The shortened spacing of the GO / PVA film after HCl acidification can be attributed to the H introduced during HCl acidification. + Caused by H + It can be absorbed by oxygen-containing groups and inhibit the cross-linking of GO and PVA.

[0427] Fig.24 b- Fig.24c shows the XPS spectra of the C1s region in the GO / PVA film acidified by 0.0% HCl, 1.0% HCl and 32.0% HCl. The C1s peaks in GO / PVA (0% HCl) with binding energies of 284.8 eV, 286.2 eV, 287.0 eV and 289.2 eV represent CC (45.29 at.%), CO (19.18 at.%), C=O (4.67 at.%), OC=O (4.84 at.%), respectively. The C1s peaks in GO / PVA (1.0% HCl) with binding energies of 284.8 eV, 286.0 eV, 287.0 eV and 289.1 eV represent CC (28.61 at.%), CO (18.50 at.%), C=O (14.91 at.%) and OC=O (5.96 at.%), respectively. The C1s peaks in GO / PVA (32% HCl) with binding energies of 284.8 eV, 285.9 eV, 287.0 eV, and 289.0 eV represent CC (28.30 at.%), CO (14.26%), C=O (20.75 at.%), and OC=O (4.49 at.%), respectively. Therefore, the ratio of CO bonds decreases after HCl acidification, while the ratio of C=O bonds increases after HCl acidification. It is reported that films with more C=O bonds exhibit higher work function and surface potential. The surface potential of the GO / PVA film analyzed by Kelvin probe force microscopy (KPFM) at room humidity (RH=55%) increases after acidification, which can be attributed to the increase in the ratio of C=O bonds after HCl acidification.

[0428] After HCl acidification, the epoxy groups can be arranged in a row, which leads to the cleavage of the CC bond. The epoxy chain tends to be oxidized to an epoxy pair and converted to a carbonyl pair because the carbonyl group is more stable under this condition ( Fig.24 d) C=O with strong polarity attracts H + and CO in forming hydrogen bonds. Therefore, the higher voltage output can be attributed to the more C=O bonds, which attract more H from the dissociation of the functional groups (-OH and -COOH). + , and leads to a larger protonation gradient for excellent electrical output. In addition, the charge carriers (H + ) density increases after acidification due to the dissociation of H in the membrane exposed to moisture. +More, which leads to a decrease in membrane resistance and an increase in current output. In order to confirm the exact functional groups that contribute to the improved voltage output, the oxygen-containing groups in the GO / PVA membranes washed with acetic acid and NaOH were also studied. The GO / PVA membrane washed with acetic acid showed CC (35.96 at.%), CO (22.28 at.%), C=O (1.27 at.%) and OC=O (6.13 at.%), while the GO / PVA membrane washed with NaOH showed CC (37.86 at.%), CO (25.24 at.%), C=O (2.74 at.%) and OC=O (2.47 at.%). The V of GO / PVA membranes washed with acetic acid and NaOH max are 0.34 V and 0.22 V, respectively, which are much lower than the V of the membrane acidified by HCl. max , because the C=O ratio in the GO / PVA membrane washed with acetic acid and NaOH is much lower. Therefore, the C=O ratio is closely related to the electrical output of the GO / PVA membrane.

[0429] First principles calculations based on density functional theory (DFT) were performed to provide atomistic insights into the observed enhancement in electrical output induced by HCl acidification of graphene oxide. Specifically, we simulated the proton binding process of O- and OH-surface functionalized graphene oxide in the presence and absence of carbon vacancies generated by acidification. Our theoretical DFT results show that the presence of carbon vacancies significantly increases the formation of hydrogen bonds between mobile protons and immobile functional groups on the surface, and the simulation results can explain the enhancement in electrical output observed in the experiment. Fig.25 A summary of the theoretical DFT results of this paper is provided in .

[0430] In the absence of carbon vacancies (V C ), the mobile protons tend to form strong chemical bonds with the O atoms on the carbon surface ( Fig.25 a). In this case, the energy corresponding to proton binding amounts to 1.12 eV / H - this makes H chemisorbed and therefore detrimental to proton migration (i.e. the interaction between O and H is too strong). At the same time, in the presence of V C In the case of defects, the interaction between mobile protons and surface O atoms becomes less strong (i.e., about 0.1 eV) because the latter are already strongly adsorbed on graphene oxide. Therefore, they do not easily interact with mobile H + Ion exchange charge ( Fig.25 b). As a result, many hydrogen bonds involving electrostatic attraction rather than complete covalent interactions are formed on the carbon surface, which facilitates proton migration for higher electrical output.

[0431] When considering the functional groups (-OH) on the carbon surface, the general conclusions are very similar to those reported in the previous paragraph. C When the carbon surface is sparse, -OH spontaneously detaches from the carbon surface when H binds ( Fig.25 c) The -OH desorption effect is driven by the formation of a water molecule, which relies on the removal of water from the relatively weak CO surface bond (i.e., E O-C ≈0.1 eV) to the OH molecular bond, and this is obviously not desirable for charge-discharge cycling purposes. In contrast, in the presence of abundant carbon vacancies, V C The nearby immobile -OH tends to form a slight hydrogen bond with the mobile proton ( Fig.25 d). In the latter case, electrons are removed from the very stable CO surface bond (i.e., E O-C ≈3.7 eV) to the covalent OH bond is energetically unfavorable, and thus the mobile H ions are captured by the functional group (-OH) via moderate electrostatic forces.

[0432] Overall, our theoretical DFT simulations reproduce the experimentally observed enhancement of the electrical output of graphene oxide induced by HCl acidification, with the increased formation of hydrogen bonds being the underlying reason.

[0433] Application Display

[0434] MEG with high voltage and current can directly power electronic devices such as memristors and sensors, which significantly improves their practical applications. To further increase the voltage or current output, MEG units are directly connected in series or in parallel. For one unit, two units, and four units, the maximum current is 9.28μA, 18.16μA, and 40.69μA, respectively. Fig.26 a). In addition, for one unit, two units, and four units, V max They are 0.85V, 1.70V and 3.38V respectively ( Fig.26 b). Therefore, the voltage and current of MEG increase almost linearly with the electrical output of a unit ( Fig.26 c), which demonstrates great potential in generating high electrical output through simple assembly of series or parallel units. The enhanced power generation performance can further broaden its potential applications, such as hydrogen catalysis.

[0435] GO / PVA films acidified with 32% HCl were also fabricated on carbon cloth for flexible device applications. The acidified GO / PVA films on carbon cloth were attached to glass bottles with different radii to study the effect of film curvature on the voltage output of the GO / PVA films. -1 、0.5cm -1 and 1.0cm -1The curvature of the membrane, V max They are 0.83V, 0.85V and 0.84V respectively ( Fig. 27 a). Thus, the acidified GO / PVA film showed stable voltage output on flexible substrates with different curvatures, which demonstrated its great potential in flexible electronic devices. In order to incorporate the GO / PVA film into flexible and wearable applications, the film should show good electrical output in mechanical motions such as bending. The acidified GO / PVA film on carbon cloth was bent from 0° to 120° in one second. The flexible MEG was able to withstand 2000 bending deformations, and V max There is no significant drop, which shows great potential in flexible and wearable applications ( Fig. 27 b).

[0436] In addition, MEG shows good charge and discharge cycling stability. MEG can be directly charged by moisture and discharged at 20 μA·cm -2 MEG exhibits a similar charge / discharge process with good stability in each cycle. The energy harvested from moisture by MEG can also be used to directly charge power storage devices, such as a commercial capacitor (20 μF) that charges to 0.80 V ( Fig. 27 c), which shows great potential in both energy conversion and storage. The electrical output of an external device powered by MEG was studied by connecting a load resistor with different resistances ( Fig. 27 d). When the load increases from 1 kΩ to 3 MΩ, the voltage across the resistor increases from 0.01 V to 0.81 V, while the current decreases from 8.55 μA to 0.27 μA. The highest output power across the load resistor is 1.36 μW with a resistance of 0.1 MΩ. In addition, a commercial pressure sensor can be directly powered by a single MEG at room humidity (55%) and generates electrical signals in response to external pressure stimulation ( Fig. 27 e- Fig. 27 f), which demonstrates great potential for powering practical devices at indoor humidity. In addition, since the electrical output is independent of the membrane area, device arrays can be easily realized by dividing the membrane into small pieces to power practical devices. The acidified GO / PVA film pattern was fabricated on FTO glass by the above method, followed by dividing the membrane into 20 units in parallel and coating Ag paste on the top side of all units as the top electrode to increase its current output. The pattern with 20 units in parallel can also be connected in series to increase the voltage output. The array (2 series × 20 parallel) can provide enough power to power a commercial computer ( Fig. 27 g).

[0437] in conclusion

[0438] In summary, this paper uses HCl-treated GO / PVA to fabricate MEG, because HCl acidification and PVA addition can improve the protonation gradient of MEG and the microstructural stability of the acidified membrane on the substrate, respectively, which is conducive to achieving high electrical output with good stability. The top surface of the acidified GO / PVA membrane is directly exposed to moisture. The bottom side is tightly fitted with the FTO glass, thus robustly preventing moisture penetration. Driven by this moisture asymmetry, electrical output is generated between the top and bottom sides of the GO / PVA membrane. The GO / PVA membrane as a functional layer outperforms the GO membrane and the PVA membrane due to its high and stable voltage output. The voltage output is closely related to the protonation gradient, which can be improved by HCl acidification and high RH. At RH = 75%, the GO / PV film acidified with 32.0% HCl generated a high voltage of 0.85 V and an excellent current of 9.28 μA (92.8 μA·cm2), and the electrical output was easily increased by connecting in series or in parallel (3.38 V or 40.49 μA for four units in series or in parallel). The voltage of the acidified GO / PVA film on the flexible carbon cloth did not drop significantly with film curvature and bending cycles, which shows great potential in flexible and wearable applications. The acidified GO / PVA film can also be easily divided into patterns to obtain higher electrical performance and successfully powered a commercial calculator, which is promising in harvesting energy from moisture and powering various practical devices.

[0439] Part 3: Samples and Results

[0440] Section 3 below describes the third series of samples and results:

[0441] Fig.28 , Fig.29 , Fig.30 and Fig.31 The results shown in are related to MEG samples treated with HNO3. The MEG samples include functional layers including graphene oxide and PVA film on FTO glass. The samples were tested (a) without acidification; (b) with acidification by HNO3 solution; and (c) with acidification by HNO3 vapor.

[0442] In the first method, for liquid acid treatment, the GO / PVA layer was immersed in a HNO3 solution (70 wt%) for 10 min. Then, the device was washed with distilled water for 10 min and dried at 50°C for 12 h.

[0443] In the second method, for steam treatment, the GO / PVA layer was suspended above a HNO3 solution (70 wt%) in a sealed chamber. The device was then washed with distilled water for 10 minutes and dried at 50°C for 12 hours.

[0444] It was found that the interlayer spacing increased after acidification (for GO, For HCl GO is For HNO3GO ). Higher interlayer spacing facilitates faster water migration.

[0445] The O / C ratio in the pristine (unacidified) GO membrane was 34.52%.

[0446] The O / C ratios in the GO films acidified by HNO3 solution and HNO3 vapor were 54.31% and 53.80%, respectively. These results demonstrate that the C=O bonds have been significantly increased by HNO3 treatment.

[0447] The electrical output of the device at 80% relative humidity is shown in Fig.30 The sample has a zinc top electrode and a carbon nanotube (CNT) bottom electrode with a thickness of about 0.5 cm 2 The sample has an area of ​​about 1cm 2 The area of ​​​​the Zn foil device is 1.6V, and the functional layer is treated with 70% HNO3. The bottom electrode is MW carbon nanotubes. For the Zn foil device, it can be seen that the voltage is very high (~1.6V), which is contributed by the redox behavior of zinc. The current is limited to the contact area of ​​Zn with GO.

[0448] Fig.31 The results show that for a 0.6 cm 2 The voltage / current curve of the sample with the top electrode of Ag paste at 70% humidity. Vmax is 0.89V; Imax is 3.21mA. After 100 minutes of operation, the current = 0.19mA.

[0449] Part 4: MEMS devices with layered structures

[0450] Section 4 below describes the fourth series of samples and results:

[0451] The following description describes other power generation cores (also referred to as moist gas generator (MEG) cores, or moist gas power generation devices, or MEG devices) with reference to the accompanying drawings.

[0452] Reference now Fig.33 , the wet gas power generation device 3300 includes a first electrode 3310 and a second electrode 3320. Disposed between the first electrode 3310 and the second electrode 3320 is a functional layer that releases charge carriers to the first electrode and the second electrode. The functional layer may also be referred to as an active layer.

[0453] Functional layer 3330 includes sublayers. Fig.33In the MEG core shown in , layer 3330 includes a first sublayer 3312 and a second sublayer 3314. The first sublayer 3332 can provide moisture to the second sublayer 3334. Moisture includes water molecules. Water molecules can exist in liquids or water vapor and in humid environments. The first sublayer 3332 acts as a moisture reservoir for the second sublayer 3334. The second sublayer 3334 is a functional sublayer that releases charge carriers based on moisture available from the first sublayer. The first sublayer that acts as a moisture reservoir can be referred to as a moisture sublayer, a moisture reservoir sublayer, or a hydration sublayer. Typically, the functional layer includes a functional group that generates charge carriers by dissociating water molecules when exposed to moisture. The first sublayer 3332 can provide moisture to the second sublayer 3334, and the second sublayer 3334 generates charge carriers based on the moisture received from the first sublayer 3332.

[0454] For example, if the second sub-layer includes a carbon-based nanomaterial, oxygen-containing functional groups in the surface of the carbon-based nanomaterial interact with water molecules from moisture and dissociate the water molecules to generate mobile hydrogen ions.

[0455] The moisture reservoir sublayer has the property of absorbing and storing moisture. The moisture reservoir sublayer can be hydrated. The moisture reservoir sublayer can provide moisture to other sublayers of the moisture power generation device.

[0456] Including a moisture reservoir (or water reservoir) sublayer in a moisture power generation (MEG) device helps control the delivery of moisture to the functional sublayer. When the functional sublayer absorbs moisture, the functional sublayer dissociates charge carriers. For example, the functional groups of the functional layer generate charge carriers by dissociating water molecules from moisture. Moisture is transferred from the moisture reservoir sublayer to the functional sublayer. The moisture reservoir provides moisture to the functional sublayer. By providing moisture from the first sublayer 3332 to the functional sublayer 3334, the functional sublayer 3334 is less dependent on absorbing moisture from environmental conditions because it can absorb water molecules from the sublayer that acts as a moisture reservoir. The second sublayer 3334 can absorb moisture directly from the environment through any surface exposed to the environment, but the second sublayer is provided with moisture from the first functional layer.

[0457] Since the second sublayer is less dependent on the environment as its sole moisture source, the moisture power generation device can generate charge under both low humidity conditions and high humidity conditions, assuming that moisture is provided from the first sublayer to the second sublayer. This results in the performance of the MEG device being less variable under varying ambient moisture conditions, because moisture delivery from the first sublayer to the second sublayer can be maintained. Water in the reservoir sublayer will evaporate at low humidity, and it will absorb water from the environment in a high humidity environment.

[0458] The moisture sublayer acts as a damper and acts as a buffer between the second sublayer (functional sublayer) and the environmental conditions. The presence of the moisture sublayer produces a more consistent moisture delivery to the functional sublayer than if the functional sublayer were completely dependent on moisture from the environmental conditions. The presence of the moisture sublayer allows the functional sublayer to receive moisture regardless of the environmental conditions to which the moisture power generation device is exposed (assuming that the moisture sublayer is fully hydrated).

[0459] The sublayer that acts as a moisture reservoir is able to retain moisture, and it can act as a pool to other layers in the moisture power generation device by providing moisture to these other layers. This sublayer can also be called a hydration layer because it can release moisture to other sublayers to hydrate those other sublayers. The first sublayer that acts as a moisture reservoir to the second sublayer can hydrate the second sublayer. Moisture can be provided from the first sublayer to the second sublayer, meaning that, assuming that sufficient moisture is available from the first sublayer, the second sublayer can be hydrated even under low humidity environmental conditions. Therefore, the first sublayer can hydrate the second sublayer under ambient or even extreme conditions (0% relative humidity (RH)).

[0460] The first sub-layer, which acts as a moisture reservoir to the second sub-layer to provide moisture to the second sub-layer, is more hydrophilic than the second sub-layer.

[0461] Fig.34 The movement of moisture 3400 from the first sub-layer 3332 to the second sub-layer 3334 is illustrated.

[0462] In some wet gas power generation devices, the first sublayer 3332 is a polymer.

[0463] Some polymers are hydrophilic polymers. Hydrophilic polymers include hydrophilic functional groups. These hydrophilic polymers can be hydrated.

[0464] Hydrophilic polymers can be efficient moisture absorbers, meaning that the polymer can absorb moisture from the environment even in a low humidity environment. A moisture power generation device including a polymer exposed to the environment absorbs moisture into the moisture power generation device even in a low humidity environment. This allows moisture to be absorbed by the polymer sublayer into the moisture power generation device. This allows the moisture power generation device to absorb moisture more easily than a device with a single non-polymer functional layer (such as GO). The efficient moisture absorption property allows the moisture power generation device to absorb water in a low humidity environment. This can improve the electrical performance of the device in a low humidity environment.

[0465] Polymers can be hydrated. They can absorb and retain water. A fully hydrated polymer layer can provide moisture to other layers of a wet gas power generation device. A hydrated polymer layer can contain abundant water that keeps the second sublayer hydrated. This property allows the polymer layer to provide moisture to other layers of the power generation device under different environmental conditions. Assuming that the polymer is fully hydrated, the polymer layer can provide moisture to other layers of the wet gas power generation device regardless of the ambient humidity conditions. For example, the polymer can provide moisture to other layers of the wet gas power generation device under low relative humidity (RH) conditions (e.g., 0%) and also under high relative humidity conditions (e.g., 100%).

[0466] Examples of the polymer include 4-phenylenesulfonic acid (PSSA), PSSNa, PAA, PVA, PSSLi, PSSK, PSSNH4, PSSMg2, PSSAl3, PSSH, chitin, chitosan, cellulose, starch, gum, alginate and carrageenan, polyamide, polyphenol, organic polyester, inorganic polyester and polyanhydride. The polymer includes a hydrogel.

[0467] Certain polymers have physical properties that make them suitable for wet gas power generation device fabrication, including being flexible, stretchable, easy to fabricate, cost-effective, semi-transparent, and able to operate at low humidity.

[0468] In some wet gas power generation devices, the first electrode 3310, the second electrode 3320, and the functional layer 3330 are arranged in a stacked orientation.

[0469] Reference now Fig.35 , Fig.35 A top perspective view of a wet gas power generation device is shown. Fig.35 It is shown for illustration purposes only and is not drawn to scale.

[0470] exist Fig.35 In the embodiment, the wet gas power generation device 3500 includes a first electrode 3510 (also referred to as a top electrode), a second electrode 3520 (also referred to as a bottom electrode), and a functional layer 3530. The functional layer 3530 includes a first sublayer 3532 and a second sublayer 3534. Fig.35 In the device shown in , the first electrode 3510 is attached to the surface 3533 of the first sublayer. The second electrode 3520 is attached to the surface 3535 of the second sublayer. Fig.35 In the device of , face 3533 and face 3535 are opposite faces of the functional layer. Obviously, the orientation of the device is not limiting, and these labels are used only for descriptive purposes.

[0471] Functional layer 3530 has a length dimension (L) and a depth dimension (D) that are much larger than the thickness dimension (E). For example, the thickness of the functional layer can be about 0.5 mm, the length can be about 1 cm, and the depth can be about 1 cm. The surface area of ​​surface 3533 and surface 3535 is large compared to the cross-sectional surface area of ​​the layer. The surface area defined by the length (L) dimension and the depth (D) dimension can be referred to as the in-plane surface. Bottom electrode 3520, second sublayer 3534, first layer 3532 and top electrode 3510 are stacked vertically, with the large surface areas of the faces connected (rather than the layers being connected in an end-to-end configuration).

[0472] The stacking configuration in which the layers are stacked vertically is beneficial because the interfaces between the layers have a large surface area (i.e., a much larger surface area than the cross-sectional surface area of ​​the layers used in the end-to-end interface connection between the layers). This large interface surface area reduces the internal resistance of the wet gas power generation device. The large interface surface area provides an opportunity for greater flow of carriers.

[0473] The sublayers are stacked vertically to form functional layers. Fig.33 and Fig.35 In the device, the sub-layers are adjacent. The adjacent layers are electrically connected.

[0474] By positioning the sublayers in an adjacent arrangement, an electrical interface is provided between the first sublayer and the second sublayer. The electrical interface facilitates direct movement of charge carriers between the first sublayer and the second sublayer. The adjacent arrangement provides. The adjacent sublayer arrangement also allows moisture to move directly between the layers.

[0475] In some examples, the functional layer is a bilayer structure having two sublayers, i.e., the first sublayer acts as a moisture reservoir to the second sublayer, which is the functional sublayer. Other devices may include more than two sublayers. In some devices, the first sublayer and the second sublayer may not be adjacent.

[0476] In some devices, the first sublayer contributes charge to the wet gas power generation device. In some wet gas power generation devices, the first sublayer can release charge carriers when the wet gas power generation core is exposed to moisture. The first sublayer can have MEG properties and release charge carriers when it is exposed to moisture. One advantage is that the second sublayer and the first sublayer are both MEG layers. This provides the following advantages: when the device is exposed to moisture, in addition to the charge carriers provided by the second sublayer, charge carriers can also be provided to the wet gas power generation device by the first sublayer. Compared with a single-layer MEG device, this increase in the number of charge carriers can increase the electrical performance (such as voltage) of the device.

[0477] In some wet gas power generation devices, the second sublayer has a net charge opposite to the charge of the charge carriers released in the first sublayer. For example, if protons tend to be released from the first sublayer, the second sublayer can be selected to have a net negative charge. In this case, graphene oxide is a candidate material for the second sublayer because it has a net negative charge (graphene oxide is also a functional layer). The net negative charge of the second sublayer is beneficial to attract positive charge carriers from the first sublayer. This charge attraction can help increase the flow of charge through the MEG device, which can improve the electrical properties of the MEG device. Examples can include increasing the voltage and current of the wet gas charging device.

[0478] The second sublayer may be a carbon-based material. For example, the second sublayer may be graphene oxide (GO). Graphene oxide includes a plurality of functional groups and when it absorbs moisture, H + Ion dissociation. Graphene oxide has a higher density than other more permeable materials such as Mxene.

[0479] Graphene oxide is a good candidate for the second sublayer because it can absorb excess water from the polymer layer. GO is also negatively charged, so it can attract generated protons from the polymer layer.

[0480] Fig.36 The MEG device 3600 is arranged to create a moisture gradient across the device. In the MEG device 3600, the second sublayer 3634 is positioned between the first layer 3632 and the second electrode 3620. The top surface 3632 of the second sublayer 3634 faces the first sublayer 3632. In the device 3600, the top surface of the second sublayer interfaces with the first sublayer. The bottom surface 3636 of the second sublayer 3634 faces the second electrode 3620. The device 3600 is arranged to prevent moisture from entering the bottom surface of the second sublayer.

[0481] exist Fig.36 , electrode 3620 extends on the bottom surface of the second sublayer. Electrode 3620 covers the bottom surface of the second sublayer 3634. Examples of suitable materials for the bottom electrode include carbon-based materials, such as carbon nanotubes or graphene. Other suitable materials for the bottom electrode include FTO, ITO, MXene, Au, Pt and carbon black.

[0482] By covering the bottom surface, the electrode 3620 reduces the penetration of moisture into the second sub-layer through the electrode 3620. Preferably, the electrode 3620 prevents the penetration of moisture into the second sub-layer. Preferably, the electrode has moisture barrier properties to prevent the penetration of moisture into the second sub-layer.

[0483] By mounting the bottom electrode 3620 on a separate substrate, additional resistance to moisture penetration can be provided. This can improve the moisture resistance properties of the bottom layer by requiring that any moisture that penetrates into the second sublayer of the functional layer must first penetrate the substrate and then penetrate the first electrode 3620 to penetrate into the second sublayer.

[0484] exist Fig.36 In the example of FIG. 36 , the electrode 3620 covers the surface of the second sublayer 3634. Fig.36 As shown in , the bottom electrode 3620 extends over the entire bottom surface of the second sublayer. This configuration covers the entire surface to prevent direct contact with moisture. As discussed above, this helps reduce the penetration of moisture over the entire bottom surface of the device.

[0485] An advantage of preventing moisture from entering the bottom surface of the second sub-layer is that a moisture gradient can be created across the moisture power generation device.

[0486] exist Fig.36 In the example of , MEG device 3600 is configured to promote the absorption of moisture into the top surface 3633 of the first sub-layer. When the device is placed in a humid environment, this configuration helps to create a moisture absorption difference between the surfaces of the functional layers. This promotes abundant moisture to be absorbed into the top surface of functional layer 3633, while no moisture is absorbed into the bottom surface of functional layer 3636.

[0487] exist Fig.36 In an embodiment of the present invention, the first electrode 3610 is configured to cover only a portion of the top surface 3633 of the first sublayer 3632. The electrode 3610 does not completely cover the top surface 3633. The electrode 3610 partially covers the top surface 3633. The remaining portion of the top surface 3633 of the first sublayer is not covered. The uncovered portion of the top surface 3633 is exposed to ambient conditions. This allows direct contact of moisture 3640 onto the top surface 3633. A larger top electrode can result in a greater carrying capacity through the electrode.

[0488] In some devices, electrode 3610 can cover the entire top surface 3633 of the first sublayer. Fig.36b The above reference is illustrated Fig.36 A wet gas power generation device similar to the wet gas power generation device described, but in Fig.36b In the device, the top electrode 3610 covers the top surface 3633 of the first sublayer. Preferably, such a top electrode should be a moisture absorber and allow moisture to penetrate the electrode and onto the functional layer. Such an electrode can be permeable. Such an electrode can be a silver nanowire.

[0489] A larger top electrode with a larger contact area (interface) with the functional layer can result in a greater current carrying capacity through the electrode joint. However, if the electrode is too large, water can be prevented from escaping from the functional layer and moisture can also be prevented from passing through the electrode contact surface.

[0490] The permeable top electrode 3610 allows moisture to penetrate the electrode and into the top surface 3633 of the functional layer. Therefore, if the top electrode 3610 is permeable, a larger top electrode can be used that covers a larger portion of the top surface of the functional layer, but still allows absorption of moisture into the top surface 3633 of the functional layer. Moisture is absorbed into the top electrode 3610 and passes through the top electrode 3610 and into the surface of the functional layer. The permeable electrode allows for an increase in the contact area between the electrode and the surface of the functional layer to help achieve higher currents. An example of a permeable electrode that may be suitable for use as a top electrode is an electrode based on silver nanowires.

[0491] More generally, examples of permeable electrodes include electrodes containing metal nanowires. Preferably, if the metal is to be used for a long time, the metal should have good corrosion resistance. The metal nanowires have a network structure, so moisture can penetrate the electrode and into the functional layer.

[0492] If the top electrode completely covers the top surface of the first sublayer (e.g. Fig.36b ) and is not permeable, it will prevent moisture from being absorbed into the top surface of the first sublayer. In such a device, moisture can be absorbed into the first sublayer from the sides of the device (and any other parts of the first sublayer exposed to ambient conditions). Fig.36b In the embodiment of the present invention, moisture 3640b and moisture 3640c can be absorbed by the surface area of ​​side 3632c and side 3236b of the first sublayer. In these cases, the surface area of ​​the first sublayer that can absorb moisture from the environment is significantly reduced compared to a device with an electrode and / or a permeable electrode that partially covers the top surface of the first sublayer. This reduces the amount of moisture that can be absorbed from the environment compared to a device with an electrode and / or a permeable electrode that partially covers the top surface of the first sublayer.

[0493] The sublayer (e.g., polymer layer) that acts as a moisture reservoir may include an ionic salt. The concentration of the salt plays an important role in device performance. The presence of the ionic salt in the polymer layer provides movable ions that can be used as a medium to strengthen the ion concentration gradient across the device. A MEG device including an ionic salt in the polymer layer may have a higher voltage output than a device without the ionic salt. Such free ions significantly enhance the conductivity of the polymer layer. Salts include NaCl and KCl. Li, Na, and K are considered to be first group alkali metals.

[0494] The presence of ionic salts within the polymer layer has several advantages. 1) Ionic salts reduce internal resistance by introducing mobile ions, which will increase power output; 2) Salts will enhance the water absorption capacity of the water reservoir sublayer; 3) Ions will respond to changes in humidity: at low humidity, ions at the interface exposed to air are activated by the loss of bound water molecules, and their ionic hydration energy is greater than that of the bottom region of the hydrogel. The momentum for ion migration is formed by such energy differences.

[0495] The sublayer that acts as a moisture reservoir can be a hydrogel layer. A hydrogel is a three-dimensional network of polymer chains. Hydrogels are hydrophilic and can absorb large amounts of water. The advantage of using hydrogels is that they have good moisture absorption properties. They can absorb moisture even in low humidity environments. Hydrogels can be hydrated and provide a moisture source to adjacent sublayers. This makes them effectively used as moisture reservoir layers (hydration layers).

[0496] Hydrogels have a three-dimensional framework. This structure provides operational durability because when the hydrogel is hydrated, the structural integrity of the hydrogel layer can be maintained even in a humid environment. This allows the MEG device to maintain performance. Hydrogels are also multifunctional in that they can be doped with various ions. These are ionic hydrogels. For example, metal ions, salts can be injected into the hydrogel. This provides flexibility in charge carriers when designing MEG devices.

[0497] The hydrogel provides excellent water retention. The hydrogel can contain induced mobile ions. The hydrophilic nature of the hydrogel with efficient moisture absorption means that the device is less restricted by the humidity conditions of the environment than a single layer, conventional MEG, and it can still generate electricity in low humidity environments.

[0498] The first sublayer may be doped with charge carriers. The introduction of additional charge carriers enables the electrical performance of the wet gas power generation device to be improved. In a high humidity environment - where there is abundant moisture and due to H + The dissociation of ions and moisture also produces abundant H + ions, the main charge carrier is H + In a lower humidity environment, due to the reduced amount of moisture, less H + The ions are dissociated, but the metal ions from the first sublayer remain mobile and thus the metal ions can contribute to the electrical properties of the MEG device.

[0499] Part 5: MEG device having a layered structure and comprising a polymer

[0500] Reference now Fig.37, the power generation core 3700 includes a first electrode 3710 and a second electrode 3730. Located between the first electrode and the second electrode is a functional layer 3730. When the power generation core 3700 is exposed to moisture, the functional layer releases charge carriers. The functional layer has a moisture generator (MEG) property. Moisture includes water molecules. Water molecules can exist in liquids or water vapor and in humid environments. The MEG property includes functional groups that generate charge carriers by dissociating water molecules.

[0501] exist Fig.37 In the example of FIG. 37 , the functional layer 3730 includes two sublayers 3732 and 3734. Other embodiments may include more than two sublayers. The sublayers are stacked between the first electrode 3710 and the bottom electrode 3720. Fig.37 In the example of , when the power generation cell 3700 is exposed to moisture, both sublayers release charge carriers. Both layers have MEG properties. Fig.37 , sublayers 3732 and 3734 include different materials. The sublayers can release the same type of charge carriers.

[0502] Sublayer 3732 is a polymer sublayer. Fig.37 In the example of , the polymer is 4-phenylenesulfonic acid (PSSA). Alternative polymer materials suitable for the polymer layer include PSSNa, PAA, PVA, PSSLi, PSSK, PSSNH4, PSSMg2, PSSAl3, PSSH.

[0503] PSSA is acidic and can be corrosive. The advantage of other polymer salt-based materials, including PSSNa, is that the material is neutral and non-acidic. Giving this structure an advantage for implementation into wearable technology.

[0504] Sublayer 3734 releases charge carriers when exposed to moisture. The moisture can be received from polymer layer 3732. Polymer layer 3732 acts as a moisture reservoir. It provides moisture and hydrates layer 3734. Fig.37 In the example of , sublayer 3734 is a graphene oxide (GO) sublayer. GO has advantages over other materials due to its rich functional groups. In other examples, sublayer 3734 can be a carbon-based material. In other examples, sublayer 3734 can be a polymer layer. Examples of suitable polymers include PVA, PAA.

[0505] MXene and oxidized MXene can also be used as sublayers.

[0506] Sublayer 3732 is adjacent to and electrically connected to sublayer 3734. The surface area of ​​the sublayers forms an interface.

[0507] The first electrode 3710 is adjacent to the polymer sublayer 3732. The first electrode 3710 is electrically connected to the polymer sublayer 3732.

[0508] exist Fig.37 In the example of , the first electrode 3710 is permeable to moisture. Moisture can penetrate the electrode 3710 and into the polymer layer 3732. Fig.37 In the example of FIG. 37 , the first electrode 3710 partially covers the polymer layer 3732. In other embodiments, the first electrode can completely cover the top surface of the polymer layer 3732. When the power generation core 3700 is exposed to moisture, the moisture can penetrate directly into the polymer sublayer 3732 through those portions of the sublayer that are directly exposed to moisture. Moisture can also penetrate into the polymer layer 3732 through the first electrode 3710.

[0509] exist Fig.37 In the example of , the first electrode 3710 is Zn foam. In other examples, the first electrode can include Ag, Zn, Zn plate, Zn foam, Al, Mg, Cu, Ni, Fe, or Ti.

[0510] Sublayer 3734 is adjacent to second electrode 3720 and electrically connected to second electrode 3720. Fig.37 In the example of , second electrode 3720 is a carbon nanotube. Electrode 3720 covers the surface of sublayer 3734. Fig.37 In the example of FIG. 37 , second electrode 3720 is isolated from moisture. Second electrode 3720 repels moisture. Moisture cannot penetrate through second electrode 3720 into sublayer 3734 .

[0511] In an example embodiment, the second electrode is a carbon nanotube (CNT).

[0512] The advantage of the stacked structure and electrode configuration of the power generation core 3700 is that when the power generation core 3700 is exposed to moisture, moisture can penetrate into the polymer sublayer 3732 through the first electrode 3710 or directly through contact with the surface of the sublayer 3732. However, moisture is prevented from penetrating into the sublayer 3734 via the second electrode. This configuration creates a moisture gradient on the power generation core. In particular, a moisture gradient is created on the functional layer 3730.

[0513] Sublayer 3732 is more hydrophilic than sublayer 3734. By positioning polymer layer 3732 in ambient (environmental) conditions rather than in GO layer 3734, wet gas power generation device 3700 absorbs more moisture from the environment than the GO layer in ambient conditions. This increases the moisture absorption efficiency of wet gas power generation device 3700.

[0514] Another advantage is that this stacked structure can have a much higher voltage output compared to a single layer of MEG. Also, the combination of two layers with different moisture absorption properties will extend the life of the MEG.

[0515] Sublayers 3732 and 3734 may have different moisture absorption properties. Fig.37 In the example of FIG. 37 , sublayer 3732 has greater moisture absorption properties than sublayer 3734 (ie, sublayer 3732 is more hydrophilic than sublayer 3734).

[0516] An advantage of sublayer 3732 having greater moisture absorption properties than sublayer 3734 is that when power generation core 3700 is exposed to moisture, sublayer 3732 can act as a moisture reservoir to sublayer 3734. Thus, moisture is absorbed into PSSA sublayer 3732. The absorbed moisture can permeate PSSA sublayer 3732 and penetrate into GO sublayer 3734 via the interface between the sublayers.

[0517] This enables the layer to operate at low humidity. The device can operate at low humidity because sublayer 3732 is more hydrophilic and is therefore able to absorb moisture from the environment even in low humidity environments. In this configuration, the moisture source for sublayer 3734 is sublayer 3732. This means that the hydration of 3734 depends on moisture from sublayer 3732, rather than the environment (except for those parts of sublayer 3734 that are exposed to the environment, such as uncovered sections or ends, in which case, in addition to the moisture received from sublayer 3732, some moisture can also be received directly from the environment).

[0518] exist Fig.37 In the embodiment of the present invention, the first electrode 3710 exhibits an electrochemical reaction when exposed to moisture. This electrochemical reaction can increase the voltage on the power generation core 3700. The electrochemical reaction can improve the electrical performance of the power generation core.

[0519] Some advantages of polymer-based MEG devices include that they are flexible, stretchable and easy to fabricate, cost-effective or translucent, and can operate at low humidity.

[0520] Advantages of this structure include operation at low and high humidity and high voltage and current output.

[0521] Manufacturing technology:

[0522] The following technologies are used to manufacture these power cells:

[0523] Carbon nanotubes (CNT), graphene oxide (GO), and poly(sodium 4-styrenesulfonate) (PSSNa) were each dispersed in distilled water by ultrasonic treatment for 30 minutes. Then, 400 μL of 20 wt.% CNT dispersion was placed on a PET (1×2 cm2 ) was dried at 50°C for 2 hours to serve as the bottom electrode. 200 μL of 2 wt.% GO dispersion was dried at 50°C for 2 hours on a CNT film (1×1 cm 2 ). Glycerol was mixed with 5 wt.% PSSNa solution in distilled water by ultrasonic treatment for 30 minutes (PSSNa: glycerol = 5:2). 200 μL of the mixed solution was placed on a PET (1×1 cm 2 ) was dried at 50 °C for 2 h and then peeled off to obtain an independent polymer film. The polymer film was stacked on top of the GO film and covered with a 0.5 × 0.5 cm 2 Zn foam was used as the top electrode.

[0524] result

[0525] Fig.38 Current characteristics of multiple samples of the power generation core are shown. The performance of the core was measured in different humidity environments (RH%). Fig.38 The current and time graphs of wet gas power generation cells with different types of top electrodes (Zn plate and Zn foam) and operated in different relative humidity environments (60% RH and 85% RH) are shown. The samples show mA range current output. High humidity and large size electrodes lead to good current output.

[0526] Fig.39 The short-circuit current of multiple power generation cells is shown. Fig.39 The samples shown in Table 3 include different sublayers X combined with a GO sublayer. Table 3 (below) shows the short circuit current of samples with different first sublayers. The sample size is 0.25 cm operated in 85% RH. 2 PSSNa shows better water absorption and lower resistance, which results in significantly higher current output. Better water absorption rate results in higher current output.

[0527] X PAA PVA GO PSS <![CDATA[l sc (RH=85%)]]> 2.5μA 1.1μA 2.1μA 1.1mA

[0528] Table 3: Short circuit current of devices with different functional layers.

[0529] Fig.40 The voltage characteristics versus time are shown for a first sample #1 having a silver (Ag) first electrode and a second sample #2 having a Zn plate first electrode. The samples include a bottom electrode of carbon nanotubes (CNTs), a first sublayer of PSSNa, and a second sublayer of GO. The sample with the Zn plate electrode shows an increased voltage of 1.44 V compared to 0.62 V from the sample with the Ag electrode at 85% relative humidity (RH). By using active metals as the top electrode, MEG / battery functionality can be achieved in a single device.

[0530] exist Fig.41 In the figure, sample 1 includes a single functional layer of PSSNa. Sample #2 includes a first sublayer of PSSNa and a second sublayer of GO. Sample #3 includes a first sublayer of PSSNa and a second sublayer of acidified GO. The combination of PSSNa and acidified GO can achieve high voltage and current. CNTs and Zn serve as bottom / top electrodes. GO film is drop-coated on CNTs; PSSNa film is a separate film on GO.

[0531] Fig.41 The electrical properties of the samples are shown in Table 4 below:

[0532] 1# 2# 3# CNT √ √ √ GO × √ √ GO acidification × × √ PSS √ √ √ Zn √ √ √ V(I) 1.16V 1.44V 1.71V(1.11mA)

[0533] Table 4: Fig.41 Electrical properties of the samples

[0534] exist Fig.42 The voltages of power generation devices with different second sublayers are shown in . The voltages of devices with ZN top electrode, PSSNa first sublayer, CNT bottom electrode and MXene, PVA, PAA and GO second sublayers are shown. Voltage: MXene (1.18V) < PVA (1.20V) < PAA (1.31V) < GO (1.44V). GO shows the highest voltage. GO has advantages over other materials due to its rich functional groups.

[0535] Fig.43 The voltage on the top layer of multiple double-layer wet gas power generation devices is shown.

[0536] Fig.44 The voltage across the different sub-layers in the electricity generating core is shown for a core comprising a GO sub-layer and a core comprising an acidified GO sub-layer. Fig.44 The samples include Zn electrode and CNT electrode.

[0537] We propose that the PSSNa layer acts as MEG and upon absorbing water PSSNa+H2O→PSS - +Na + (MEG).

[0538] This paper believes that Zn foam electrode according to Zn+2H2O→Zn 2+ +H2+2OH - (Battery) Act as a battery.

[0539] This paper believes that when the GO layer absorbs water, -COOH→-COO - +H + (MEG) acts as MEG.

[0540] Fig.45The electrical performance of multiple wet gas power generation cells with different top electrodes is shown. All samples include PSSNa and GO sublayers and CNT bottom electrodes. The sample with Zn top electrode shows the highest voltage at 1.4V. 2 MEG+1 cells are also shown.

[0541] Fig.46 Voltage results for other samples are shown. Sample #1 includes a PSSNa sublayer and a GO sublayer treated with plasma or UV. The top electrode is Zn, and the bottom electrode is CNT. Sample 2 is a stacked MEG with a double layer of PSSNa and GO. GO typically has low power output only at low humidity, while PSSNa can work at low humidity. Therefore, the combination of the two materials in a single MEG core enables effective operation at low and high humidity. On the other hand, polymers may deform at high humidity, so excess moisture in the polymer should be transferred to other places to extend retention. Sample #2 includes a Zn top electrode and a CNT bottom electrode.

[0542] exist Fig.47 In the example of , a single functional layer is located between the Ag top electrode and the CNT bottom electrode. Several samples were tested using different PSSX polymers. + After replacement with other ions, a voltage decrease is shown.

[0543] Part 6: MEG device having a layered structure and including a hydrogel layer:

[0544] A high performance MEG having a double layer structure is now described, in which a hydrogel layer having hygroscopic LiCl is included to improve the electrical output performance and long-term operational durability of a wet gas power generation device. The hydrogel layer forms the first sublayer of the functional layer of the device. Reference Fig.36 The MEG device structure shown in the following example, the first sublayer 3632 is a hydrogel layer with hygroscopic LiCl, and the second sublayer (functional layer) 3634 is a graphene oxide layer. The bottom electrode 3620 is a carbon nanotube. The top electrode 3610 is Ni foam. The manufacturing process is as follows. A carbon nanotube (CNT) dispersion is coated on a polyethylene terephthalate (PET) film (1 cm×2 cm) as a bottom electrode. A GO layer (1 cm×1 cm) on top of the CNT substrate is obtained by drying 100 μL of a 2wt% GO dispersion at 50°C. The upper hydrogel layer is obtained by drop-coating the prepared hydrogel solution on top of the GO layer. After gelation is completed, a piece of Ni foam (0.2 cm×0.5 cm) is placed on the hydrogel as a top electrode.

[0545] The ionic hydrogel-based MEG (HMEG) can maintain a continuous open circuit voltage (V) of 0.6 V under room conditions. OC) for more than 1400 hours and generated 1.2 mA / cm due to the excellent water retention capacity and mobile ions caused by the designed hydrogel. 2 High short-circuit current (I sc ) and 71.7 μWcm -2 The maximum power density of HMEG is 1.2 V. Compared with conventional MEG, the device is less restricted by working conditions, and it can still generate electricity in harsh environments, such as 50°C (15% RH) and -20°C (10% RH). In addition, HMEG can even deliver an ultra-high voltage of 1.2 V for more than 10 h at 0% RH.

[0546] result:

[0547] Power generation performance. HMEG can operate in complex environments (e.g., hot, dry, and cold) and exhibits long-lasting output performance and self-recovery ( Fig.48 a- Fig.48 c). The functional layer consists of two sublayers, namely the GO bottom layer (second sublayer) and the hydrogel upper layer (first sublayer) ( Fig.48 d). The layer is prepared by a drop coating method which is easy to do. Specifically, the prepared hydrogel solution is dropped onto the bottom layer ( Fig.53 The precursor self-gelates by forming hydrogen bonds between glycerol and the hydroxyl groups of PVA and coordination bonds between the hydroxyl groups and the added ions ( Fig.54 Unlike the deliquescent LiCl powder, the PVA-LiCl hydrogel showed no physical changes after exposure to ambient conditions, suggesting that the PVA-LiCl hydrogel may be suitable for long-term use ( Fig.55 ). In addition, the formed hydrogel contains abundant water to keep the underlying GO hydrated ( Fig.48 d). Fig.48 As shown in e, the proposed HMEG exhibits excellent stability in long-term output performance, which can maintain an open circuit voltage (V) >0.6 V at 45% ± 10% RH. OC ) for more than 1400 hours and continuously generated current for more than 140 hours. The changes in the electrical signals in the curves are mainly attributed to environmental fluctuations in ambient conditions during the long-term measurement period. HMEG demonstrated superior overall performance ( Fig.48 f). More surprisingly, the device was also able to generate electrical signals at high temperature and low humidity (50°C, 15% RH) for more than 150 hours ( Fig.56 ).

[0548] Similar to other conventional MEGs, RH is a key factor affecting the power generation performance of HMEGs. However, HMEGs perform differently in response to RH changes. Fig.49 a. Fig.49As shown in b, the voltage output is inversely proportional to RH, and higher current output can be achieved by increasing RH. If the RH is above 65%, a drop in voltage can be observed. Interestingly, the maximum V is recorded at 0% RH. OC ( Fig.49 a. Fig.49 b) and the voltage gradually reaches and remains above 1V for more than 10 hours ( Fig.57 ). On the other hand, Fig.49 The dynamic monitoring of the voltage output under varying RH is shown in c, and it is noted that a small burst in voltage is observed when the RH reaches 85% (indicated by the arrow). This is attributed to the transient accumulation of water within the hydrogel, which facilitates the hydrolysis of PVA into mobile ions (H + ), thus improving device performance in a short period of time. However, too many ions can lead to a collapse of the ion concentration gradient, resulting in a continuous degradation of performance. As a control experiment, both the current and voltage output of the device composed of a single GO layer showed a positive relationship with increasing RH ( Fig.58 In particular, negligible power generation was observed under the harsh condition of 0% RH ( Fig.58 and Fig.59 Since the dry GO layer possesses no water intrinsically, significant RH is required to initiate the ionization of functional groups (e.g., -COOH) within GO to release mobile H + This result strongly suggests that the hydration state of the GO layer determines the device performance. Therefore, the additional layer of ionic hydrogel can significantly help to hydrate the GO layer under ambient or even extreme conditions (RH of 0%) due to the abundant water within the hydrogel.

[0549] In addition to indoor conditions, measurements were also conducted in a refrigerator and an oven to simulate harsh conditions. The hydrogel not only exhibits antifreeze properties due to the inclusion of glycerol, but also exhibits tolerance to high temperatures by adding LiCl salts ( Fig.60 ). Therefore, the function of HMEG in power generation can be maintained regardless of the environment ( Fig.48 a). Since ion migration is affected by temperature, device performance changes in the corresponding environment. In particular, ion movement becomes more intense at high temperatures ( Fig.61 ), therefore, it can be seen that at the oven (50°C), HMEG shows a higher V OC and short-circuit current (I SC ), 0.7V and 340μA respectively. Although the mobility of ions at subzero temperatures is significantly lower than that at room temperature, the device can still generate a voltage output of 0.4V and a current output of 75μA ( Fig.49d). In addition, HMEG exhibits excellent self-recovery to meet the needs of recycling. Especially for applications in hot and dry areas, the weight loss of hydrogel is inevitable due to the evaporation of water. The recovery of the lost content is a key factor in achieving the recycling function. Therefore, HMEG in the original state was measured in the ambient environment and in the oven to evaluate the recyclability of the device. Fig.49 As shown in Fig. e, the weight of the device decreases after each dehydration cycle in the oven. Regardless of the thickness of the coated hydrogel, all HMEGs show the ability to recover weight by absorbing ambient moisture. Such self-recovery properties benefit from the superior water absorption capacity of the hydrogel. In addition to weight recovery, the current also has a similar recovery trend after absorbing moisture, as shown in Fig. Fig.49 f. The recovery capacity increases with the concentration of hygroscopic LiCl salt. Due to the excellent water absorption, 100% water content compensation and 80% current output recovery were achieved in HMEG-4.8% LiCl. Regarding HMEG-0% LiCl, the lower water absorption capacity limits the current recovery, making it unsuitable for long-term use. In addition, detachment from the substrate ( Fig.62 ), while the gel with a higher concentration of LiCl (7.2%) remained undried after 1 day and had a high viscosity. Therefore, a concentration of 4.8% LiCl was selected for the entire experiment. The introduction of LiCl plays a role in imparting improved water absorption capacity to the hydrogel, which will be further discussed in the context later. At the same time, the change in output voltage showed a stable trend in three operation cycles, indicating good stability under different conditions ( Fig.63 ). The water retention capacity was also greatly improved by adding LiCl salt. After 14 days, only 65% ​​of the weight was retained in HMEG-0% LiCl, while the device with 4.8% LiCl could hold its weight at ambient conditions ( Fig.64 ). It has excellent water retention capacity and can maintain the performance of the device for a long time. Figure 2 As shown in g, HMEG-4.8% LiCl was maintained and exposed to ambient conditions without sealing for 4 months (120 days), and no significant degradation was observed (-96% retention), demonstrating its excellent stability in power generation.

[0550] The power output of HMEG was further evaluated under different external loads. Figure 2 As shown in Figure 3, when the load resistance increases from 1Ω to 2.5MΩ, the voltage output increases while the current output decreases. 71.7μW / cm2 is achieved at a load resistance of 4670Ω. 2 The maximum power density ( Fig.65), which is different from most inorganic-based MEGs reported recently ( Figure 2 i and Supplementary Table 1) are the best results.

[0551] Factors affecting output performance. As mentioned earlier, the device was designed to have a double-layer structure with a bottom layer of GO and an upper layer of PVA-LiCl hydrogel. It should be noted that the device consisting of a sole GO layer or a sole hydrogel layer showed a gradual degradation of the voltage output, which is certainly not suitable for long-term use ( Fig.66 ). One of the reasons could be the lack of management of ion diffusion. Since hydrogels with LiCl possess excellent water absorption capacity, the ion concentration gradient across the hydrogel can easily collapse over time. In this paper, a double-layer structure with stable output is proposed, in which the hydrated GO layer with negatively charged properties helps to attract positively charged mobile ions (e.g., H + ), such as a shielding layer for power generation. In this case, the effect of the layer on the performance of the HMEG was studied. For the bottom GO layer, the layer thickness can be controlled by using different volumes of GO solution. The effect of GO layer thickness on voltage is not as obvious as its effect on current output, such as Fig.50 As shown in a. For different layer thicknesses, the voltage remains above 0.6V. In general, the device voltage is dominated by the ion concentration gradient between the upper and lower surfaces of the device. Due to the added hydrogel, the bottom GO layer is fully hydrated, so the ion concentration gradient within the GO layer is irrelevant regardless of the GO thickness. Instead, the current of the device increases greatly as the GO layer becomes thicker and becomes saturated at ~120μA. This can be attributed to more mobile ions from functional groups in thicker GO films. However, when the GO thickness is further increased, a degradation of the current is observed, which is attributed to the long migration distance of the mobile ions. At the same time, the thickness of the hydrogel layer was also studied. Similar to the GO layer, due to the more charge carriers (e.g., Li + ), the hydrogel thickness has a great influence on the current output ( Fig.67 ).

[0552] In addition, the concentration of the added salt also plays an important role in the device performance. The presence of ionic salts provides the HMEG with mobile ions that can act as a medium to enhance the ionic concentration gradient across the device. Therefore, it can be seen that the HMEG has a higher voltage output than the device without ionic salts, such as Fig.50 In particular, such free ions significantly increase the conductivity of the hydrogel. The device resistance obtained from the EIS measurement reflects that the hydrogel with 0% LiCl has a 10-fold higher resistance than the hydrogel with 1.2% LiCl ( Fig.50c). As the concentration increases to 4.8%, which is selected as the optimal concentration in this paper, the resistance of the hydrogel is further reduced. The reduction in resistance facilitates ion migration, thereby improving the current output of the device. Thus, when 4.8% LiCl is used in HMEG, an excellent current signal of ~120 μA is recorded ( Fig.50 b). In addition, the water absorption capacity of the hydrogel was also improved by adding salt. Benefiting from the hygroscopic properties, LiCl can significantly absorb moisture and bind to water molecules. Regardless of the concentration of added LiCl, the dehydrated HMEG also exhibited the ability to absorb water from moisture ( Fig.50 d). However, there is a clear increase in functionality that is proportional to the concentration of added salt, and the water uptake of the best design is 3 times higher than that of the unsalted hydrogel and pure GO ( Fig.50 d and Fig.68 ). The enhanced water absorption capacity is beneficial to realize the proposed recovery function of HMEG, which facilitates water recovery to recharge the electrical properties.

[0553] However, if Fig.50 As shown in Fig. e, higher weight loss is seen at the hydrogel with higher ion concentration after sedimentation at 50°C. This is because during the gelation process, more ions are present to interact with the water molecules in the hydrogel, resulting in more stored water ( Fig.69 ). In contrast, less water is present in low concentration hydrogels, which indicates that less water will be evaporated during operation. Generally speaking, there are three states of water in hydrogels, namely bound water, free water, and intermediate water. Water that forms strong hydrogen bonds with polymer chains is referred to as bound water, which requires the highest activation energy to break the bonds before escaping from the hydrogel. 47 Free water naturally appears as bulk water, while intermediate water is water with weak or no hydrogen bonds. 48 Such water states are characterized by tracking the OH bonds with Raman spectroscopy. Fig.50 f(i) shows 3515cm -1 and 3630cm -1 The Raman shift of indicates the presence of intermediate water within the hydrogel. As mentioned earlier, the addition of salt can form a complex with the polymer chains, thereby leading to an increased amount of intermediate water by reducing the formation of hydrogen-bonded water. 50 In other words, the amount of intermediate water within the hydrogel is proportional to the salt concentration. Due to its less constrained nature, it is reported that intermediate water evaporates with minimal energy requirements. 51For this reason, a higher amount of water loss can be seen in the hydrogels with higher salt concentrations. The differences indicated by the Raman spectra of the hydrogels also show good agreement with the findings. The ratio of intermediate water increased from 17.9% to 25.6% ( Fig.50 f(ii) and Fig.70 ). Despite the weight loss due to water evaporation at high temperatures, ionic hydrogels exhibit the function of recovering weight by trapping water vapor, e.g. Fig.50 As shown in e. A higher efficiency of recovered water can be obtained by increasing the ion concentration, which is a prerequisite for effective electroregeneration.

[0554] The effect of the type of hygroscopic salt should also be emphasized, and two other common hygroscopic salts, NaCl and KCl, are added to the system. Similar to Li, Na and K are also considered to be Group 1 alkali metals. Figure 3 As shown in Fig. 5, HMEG with LiCl has the best performance in water absorption, followed by NaCl and KCl. This can be attributed to the + and K + In comparison, Li + The hydration degree of Li+ is the highest, which is caused by the smaller hydrated ion radius (Supplementary Table 2), and thus more water molecules can be surrounded by the ion. In addition, the small hydrated ion radius enables Li+ to have a highly efficient transport rate compared with Na+ and K+. Therefore, it was monitored that the device with Li+ ions showed the highest current output, followed by Na+ and K+. + and K + ion( Fig.50 h). The voltage performance and corresponding water absorption capacity of different ionic hydrogels also have similar trends ( Fig.50 h). The poor water uptake in the hydrogels with KCl and NaCl inhibits the dissociation of mobile ions and thus limits the ion concentration gradient across the device.

[0555] Since the top electrode acts as a current collector reflecting the effective working area, the electrode dimensions were investigated. Fig.67 As shown in c, the current output is shown to be proportional to the working area of ​​the electrode, increasing with increasing electrode size from 0.04 cm 2 Increase to 1cm 2 , the current output increased from about ~80 μA to ~1 mA. In contrast, the voltage had less dependence on the electrode size and remained at ~0.6 V. In addition, the type of electrode material also plays an important role in determining the device performance ( Fig.71). A symmetric structure was constructed by designing both the top and bottom electrodes with CNT sheets, and an asymmetric structure was also developed using materials different from CNTs (e.g., Ni, Ag, and Cu). The symmetric structure was able to generate a V of 0.35 V under ambient conditions. OC The generated electrical signals from the symmetric design also confirmed that the electricity was induced by the diffusion of ions dissociated from the functional materials in the HMEG, which was stimulated by the moisture in the environment. When it comes to the asymmetric structure, among the selected metal electrodes, the HMEG with Ni electrode has the best performance, followed by Cu and Ag ( Figure 2 a. Fig.71 ). The difference in electrical output can be attributed to the difference in work function between the two electrodes (Ni, 5.35eV; Cu, 4.94eV; Ag, 4.74eV). Specifically, a Schottky contact is formed within a device with different electrodes, thus limiting ion migration in a unique direction. Therefore, the greater the difference in work function, the better electrical output can be obtained.

[0556] Mechanism of hydrogel formation. FTIR spectroscopy was used to analyze the molecular interactions in the hydrogel ( Fig.51 a) A characteristic peak of PVA is at 3293cm -1 At 1422 cm -1 and 2925cm -1 The characteristic peaks at 3273 cm-1 are related to the stretching vibrations of -CH and -CH2, respectively. In contrast to the other characteristic peaks, the wavenumber of the -OH peak shifts to 3273 cm-1 after the addition of LiCl. -1 , indicating the strong interaction between the added ions and the polymer groups. In particular, Li + ions can form complexes with hydroxyl groups through coordination bonds. + The ions bind to the polymer chains to help form the hydrogel. Fig.51 The XRD pattern in b also confirms that the hydroxyl groups of PVA are bound to the Li + The diffraction peaks at ∼19° and 20° are assigned to PVA plane and (101) plane. The peaks near 40°-43° are closely related to (111), (210) and The diffraction peaks above were associated with the crystal plane. However, after the introduction of LiCl salt, the intensity of the above diffraction peaks was significantly reduced. The reduction in crystallinity indicates a strong interaction between the polymer chains of the PVA-glycerol matrix and the LiCl salt. This interaction interrupts the crystallinity of the polymer matrix by destroying hydrogen bonds. It is noted that no crystallization peak of LiCl was detected in the hydrogel with 4.8% LiCl, confirming the uniform formation of the ionic hydrogel. In addition to gelation, LiCl also contributes to the functionality of the hydrogel. First, in the FTIR at 1650cm -1 The water peak at 400 nm showed a gradual increase after the addition of salt, revealing an increase in the water content in the hydrogel. 2D Raman mapping was also performed to assess the water content within the hydrogel, which was performed by analyzing the intensity of the OH-stretching peak. Fig.51 As shown in c, the hydrogel with LiCl is significantly richer in water than the hydrogel without LiCl. At the same time, the higher concentration of LiCl leads to a larger water content in the hydrogel. The added ions can interact strongly with water molecules, among which Li + Ions and Cl - The ions can bind to four water molecules and six water molecules, respectively. Therefore, water can be confined within the hydrogel and prevented from evaporating under room conditions, contributing to excellent water retention capabilities. Fig.64 As shown in , the addition of LiCl salt can slow down the evaporation of water content within the hydrogel, and more than 95% of the weight can be maintained in a device with 4.8% LiCl within 14 days. In addition, the structure of water molecules is interrupted by ions, thus hindering the formation of hydrogen bonds between water molecules at sub-zero temperatures. Therefore, the hydrogel exhibits antifreeze properties to generate electricity at low temperatures (-20°C) ( Figure 2 d. Fig.60 ).

[0557] Proposed power generation mechanism. During the fabrication process, the hydrogel solution is drop-coated directly on top of the GO layer, resulting in the formation of interfacial hydrogen bonds between the two layers. Due to the significant hydrophilicity of GO, water molecules inside the hydrogel solution can easily hydrate and penetrate the GO layer. On the one hand, the oxygen-containing functional groups (e.g., -OH and -COOH) within the GO layer can be dissociated into mobile H + ions and an immovable skeleton. Therefore, hydrated GO possesses negatively charged properties and shows potential in capturing counter ions. On the other hand, the hydration process expands the interlayer spacing between GO nanosheets, which facilitates ion separation and allows more ions to migrate from the hydrogel. Fig.51 d and Fig.72As shown in Figure 2, XPS measurements were performed to examine the elemental composition of the underlying GO. The peaks at ~55 eV and 198 eV correspond to Li 1s and Cl 2p, respectively. The peak of Cl 2p is stronger than that of Li 1s, suggesting that more Cl is detected within the GO layer. + ions. This observation further confirms that Li + The formation of coordination bonds between the ions and the hydroxyl groups will partially + ions are confined within the hydrogel layer. In contrast, Cl + ions are not bound to the functional groups of PVA, therefore, in the GO layer, Cl - Possessing an atomic ratio higher than Li + In addition, EDS mapping also confirmed the presence of Cl elements in the GO layer, revealing that Cl - Ion penetration from the hydrogel to the GO layer ( Fig.73 ). Taking all into account, it is shown that the deposited hydrogel layer can hydrate the GO layer and leave the ions as residues. To determine the involvement of residual ions, the output performance of the GO layer in the original state and the GO layer containing ions were compared at 45% RH. The GO layer containing ions was obtained by peeling from the ionic hydrogel, and clear hydration marks were observed on the GO layer ( Fig.74 a). The voltage of GO containing ions shows an increase from 0.4 V to 0.6 V, while the current is 5 times higher, reaching 1 μA ( Fig.74 b). It can be seen that the residual ions promote the performance of the GO layer. The details will be discussed in the corresponding context below.

[0558] Similar to conventional MEG, the formed ion concentration gradient governs the power generation in HMEG. The mobile ions within the HMEG migrate from the top side to the bottom side of the device under the concentration gradient, inducing a potential difference. In contrast, electrons are collected at the top electrode, indicating the generation of current. However, the behavior of HMEG is different from that of other MEGs that are positively correlated with RH. The underlying mechanism of HMEG can be explained in three different states according to the RH conditions, such as Fig.51 As shown in f.

[0559] i) Under ambient conditions (e.g., 45% RH), the hydroxyl groups in PVA can dissociate into mobile H + ions and immobile -O - The skeleton and the mobile H + The ions can drive hopping through interfacial hydrogen bonds via the Grotthuss mechanism. Meanwhile, the immobile -O- groups can assist the hopping migration of hydrated Li+ ions by forming complexes, which significantly increases the conductivity of the hydrogel. Regarding the effect of the overhydrated bottom GO layer, the dissociated H+ The ions have a limited contribution to the total voltage because the ion concentration gradient is weakly constructed across the overhydrated GO layer. Instead, the dissociated free ions contribute to the enhanced current output. In this case, the residual Li + ions serve as additional mobile ions to migrate through the GO layer, with their diffusion guided by the negatively charged surface of the hydrated GO. - Ions also accumulate within the GO layers, facilitating the construction of a larger potential difference across the device. In addition, the increased interlayer spacing of the hydrated GO layers provides larger nanochannels to enhance ion transport. The synergistic effect of higher potential difference and faster ion diffusion boosts the power output of the device under room conditions.

[0560] ii) In moisture-rich conditions (e.g., 85% RH), the superior moisture absorption capacity of the ionic hydrogel allows the collection of large amounts of water from the surrounding environment. Initially, the surface exposed to moisture will release H from the hydroxyl groups as usual. + ions. This could explain the short-term voltage increase observed at 80% RH. Over time, excess water is retained within the hydrogel, where a large amount of H + Ions accumulate on the hydrogel layer, while the underlying GO layer remains overhydrated. In this regard, the device lacks an ion concentration gradient, resulting in a continuous drop in output voltage ( Figure 2 c).

[0561] iii) In a low humidity environment (e.g., 0% RH), the voltage of HMEG was observed to gradually increase, rather than decrease as in other reported MEGs. In order to exclude the possibility that the voltage increase was caused by electrochemical reactions, CV measurements were first performed. The CV curves revealed that no significant electrochemical reactions occurred regardless of RH ( Fig.75 a). In addition, the top Ni electrode is replaced by an Ag plate, which is more inert than Ni. Fig.75 As shown in b, the voltage of the HMEG with Ag electrodes is similar to that of the device with Ni, and it also gradually increases at 0% RH. The voltage of each individual layer is measured with Ni electrodes, as shown in Fig.51 e. The voltages of the GO and hydrogel layers are 0.62 V and 0.6 V, respectively. And the device with a double-layer structure exhibits a voltage of ~1.2 V, which is consistent with the combined voltage of the hydrogel and GO devices connected in series. Note that the water in the hydrogel tends to evaporate in a low RH environment to reach equilibrium. In this case, the water molecules and Li +The bonds between ions are broken, allowing water molecules to evaporate naturally. It is reported that ions bound to more water molecules have lower ion hydration energy. During water evaporation, due to the loss of bound water molecules, ions at the interface exposed to air are activated, and their ion hydration energy is greater than that of ions at the bottom area of ​​the hydrogel. The momentum for ion migration is formed by such energy differences. Ions (Li + ) is used as a charge carrier instead of H + Ion, H + The ions dissociate from the hydrolysis of the PVA hydroxyl groups at 45% RH. In contrast, the ability of the device with 0% LiCl to generate electricity is limited when exposed to low humidity due to the lack of mobile Li at 0% RH. + ions. As a result, the hydrogel layer with LiCl was able to retain the output even at 0% RH. At the same time, Li released from the ionic hydrogel + The number of ions increases over time, which can be reflected in the continuous increase in the output voltage. For the control experiment, HMEG sealed with a waterproof membrane and HMEG with 0% LiCl were measured at 0% RH, respectively. Fig.51 As shown in g, both HMEGs show a stable voltage only at 0.5V, which is similar to the voltage under ambient conditions (45% RH), instead of increasing to above 1V in the unsealed HMEG with 4.8% LiCl. For the sealed HMEG, water evaporation from the hydrogel is prevented while the water is stored in the sample, providing an ambient-like environment to maintain the device performance at 0.5V. Despite the evaporation of water from the unsealed HMEG-0% LiCl, negligible improvement was observed, further confirming that the added salt is also important because it acts as a donor of charge carriers when water evaporation occurs. Taking all into account, water evaporation at 0% RH affects the electrical signal, while the introduced salt dominates the voltage increase.

[0562] In addition to the hydrogel, the GO layer under this condition contributes to the overall output performance, with similar properties to GO containing ions at 45% RH ( Fig.74 b). First, the residual ions mentioned above in the GO layer increase the corresponding voltage from 0.4V to 0.6V ( Fig.51 e). Water evaporation at 0% RH can alleviate the over-hydration state of the GO layer. Instead of acting as an ion migration path under ambient conditions, the GO layer is reactivated under low humidity conditions to act as a proton donor and expand the potential difference, thereby improving the output performance.

[0563] Applications of HEMGs. Despite the considerable output of individual units, the overall power output needs to be further increased to drive commercial electronic devices. The facile fabrication in this study provides the feasibility of scaling up the device proportionally to increase the electrical output. Fig.52 As shown in a, 2 devices connected in series can generate twice the output voltage, reaching 1.2 V. Such voltage can be further increased by connecting more units, which shows a linear relationship with the number of devices ( Fig.52 a. Fig.52 b). In addition, a large-scale series connection of 168 cells was achieved on a flexible PET substrate (210 mm × 297 mm), capable of outputting a total voltage of ~97 V ( Figure 5 b. Figure 5 c. Fig.76 a). More importantly, the large-scale device exhibits over 95% voltage retention during mechanical bending, thus demonstrating great potential as a power source for wearable electronic devices ( Fig.77 The "UNSW" pattern designed with 39 LEDs can be directly illuminated by the power supplied from 168 HMEGs ( Fig.52 d. Fig.76 b). Commercial capacitors can also be used to store the generated power for use in other electronic devices. Under ambient conditions, 100μF and 470μF capacitors can be charged to 0.58V (1 cell) and 30V (168 cells), respectively. Fig.52 e). In addition, the stored energy can be used to generate pulse trains to achieve the typical reinforcement behavior of synaptic devices ( Fig.52 f). In addition, the charged capacitors can be used to power electronic devices such as smart windows and e-ink screens to display designed graphics ( Fig.52 g) In Fig.78 A schematic diagram of the circuit of a MEG-powered electronic ink display is shown in FIG.

[0564] discuss

[0565] In summary, this paper reports a high-performance hydrogel-based humid vapor generator (HMEG). The fabricated device is able to generate 1.2 mA / cm under room conditions. 2 Ultra-high I SC and can continuously generate 0.6V V OC More than 1400 hours. The device shows the potential to operate under a wide range of ambient temperature (-20℃-50℃) and RH (0%-85%), demonstrating all-weather usability. Compared with conventional MEG, the proposed HMEG delivers higher voltage at lower humidity, with a persistent V of 1.2V recorded at 0% RH. OC. Due to the abundant water inside the hydrogel, the device can have less dependence on the surrounding RH, and the reduction of RH can trigger the evaporation of water within the hydrogel, thereby improving the performance of the device at 0% RH. In addition, the excellent water absorption capacity of the hydrogel with LiCl also gives the device the ability to recover moisture loss by absorbing ambient moisture. Such properties contribute to the advantages of the proposed HMEG in terms of recycling. With the help of easy-to-achieve fabrication, a high voltage of 97V was demonstrated by scaling up the number of cells in series, and this voltage could be maintained after mechanical bending. These excellent properties of HMEG enable it to become a promising and sustainable power source for a wide variety of electronic devices. This study also provides insights into the design of devices for wet power generation and other fields.

[0566] method

[0567] Material

[0568] Polyvinyl alcohol (PVA, #P1763), glycerol (#G5516), lithium chloride (LiCl), and graphene oxide (GO) were provided by Sigma-Aldrich. Nickel (Ni) foam, silver (Ag), and copper (Cu) plates were purchased. The commercial carbon nanotube slurry was not further treated, and deionized water was collected from a Milli-Q water purification system.

[0569] Synthesis of hydrogel

[0570] 15wt% pure PVA solution was obtained by dissolving PVA powder in deionized water at 95°C under magnetic stirring. After collecting the transparent and bubble-free PVA solution, 20wt% glycerol was added for further stirring. Finally, LiCl powder was mixed with the prepared mixture to obtain PVA-LiCl hydrogel solution. Different amounts of LiCl (0, 1.2%, 2.4%, 4.8% and 7.2%) were added to the system.

[0571] Manufacturing of HMEG

[0572] Carbon nanotube (CNT) dispersion was coated on polyethylene terephthalate (PET) film (1 cm × 2 cm) as the bottom electrode. The GO layer (1 cm × 1 cm) on the CNT substrate was obtained by drying 100 μL of 2 wt% GO dispersion at 50 ° C. The upper hydrogel layer was obtained by drop-coating the prepared hydrogel solution on the GO layer. After gelation was completed, a piece of Ni foam (0.2 cm × 0.5 cm) was placed on the hydrogel as the top electrode.

[0573] Characterization

[0574] Prior to characterization, HMEG was dried in a vacuum oven for 12 hours to eliminate the water content in the hydrogel. Fourier transform infrared spectroscopy (FTIR, PerkinElmer spectrum 100) was performed to study the interaction between additives and functional groups. The morphology of HMEG was observed by scanning electron microscopy (SEM, FEI Nova NanoSEM 450). An Autolab (PGSTAT302N) workstation was used for electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) measurements. The state and amount of water in the hydrogel were evaluated using a Raman spectrometer (Renishaw inVia Reflex) at a wavelength of 532nm. The elemental composition of HMEG was analyzed by energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). A Cu Kα radiation source was used. The crystallinity of the hydrogels was analyzed by X-ray diffractometer (XRD) at a scanning rate of 2° / min.

[0575] Water absorption capacity

[0576] Before measuring the water absorption capacity, the formed hydrogel was dried in an oven (50°C, 15% RH) to remove the internal water content. The dried hydrogel was settled at 45% RH for water absorption. The water absorption capacity was then calculated according to the following equation, where W a , W f and W i The water absorption capacity, the weight of the hydrogel after absorption at the corresponding time and the initial weight of the dried hydrogel are represented respectively.

[0577]

[0578] Electrical performance measurement

[0579] The electrical output of the device is measured by a Keithley 2400 source meter. When measuring the short-circuit current, the source voltage is set to 0V. In contrast, the open-circuit voltage is measured at a source current of 0A. The relative humidity is controlled by a N2 gas flow through the chamber of DI water. In order to perform cyclic measurements, the sample is connected to the source meter and placed in an oven with a set temperature and RH of 50°C and 15%, respectively. After a measurement cycle in the oven, the sample is reset to ambient temperature (25°C and 45%) to absorb moisture to achieve a recovery step, followed by recording the instantaneous voltage. For sub-zero temperature measurements, the device is placed in a refrigerator for 10 minutes before measurement to reach equilibrium conditions.

[0580] It should be understood that, if any prior art publication is referred to herein, such reference does not constitute an admission that the publication forms part of the common general knowledge in the art in Australia or any other country.

[0581] Certain features described in the examples and samples described above may be used with other specific examples, such as electrodes.

[0582] In the following claims and the foregoing description of the invention, unless the context requires otherwise by explicit language or necessary implication, the word "comprise" or variations such as "include" or "including" are used in an inclusive sense, that is, to specify the presence of stated features but not to exclude the presence or addition of further features in various embodiments of the invention.

[0583] It should be understood that the foregoing description refers only to the preferred embodiments of the invention and that changes and modifications may be made thereto without departing from the spirit and scope of the invention, the scope of which should be determined in accordance with the following claims.

Claims

1. A wet gas power generation device, comprising: a first electrode and a second electrode; as well as a functional layer disposed between the first electrode and the second electrode, the functional layer releasing charge carriers; The functional layer comprises at least two sublayers: a first sublayer that acts as a moisture reservoir to a second sublayer to provide moisture to said second sublayer; The second sublayer generates charge carriers based on moisture available from the first sublayer.

2. The wet gas power generation device according to claim 1, wherein: The first sublayer includes a polymer.

3. The wet gas power generation device according to claim 1 or 2, wherein: The first electrode, the second electrode, and the functional layer are configured in a stacked arrangement.

4. The moisture generating device according to claim 1, 2 or 3, wherein: The sub-layers are arranged in a stacked configuration to form the functional layer.

5. The moisture generating device according to claim 1, 2, 3 or 4, wherein: The first sublayer and the second sublayer are adjacent sublayers within the functional layer.

6. The moisture generating device according to any one of claims 1, 2, 3, 4 or 5, wherein: When the moisture power generating core is exposed to moisture, the first sublayer releases charge carriers.

7. The moisture generating device according to any one of claims 1, 2, 3, 4, 5 or 6, wherein: The second sublayer has a net charge opposite to the charge of the charge carriers in the first sublayer.

8. The wet gas power generation device according to any one of claims 1 to 7, wherein: The second sublayer includes a carbon-based material.

9. The wet gas power generation device according to any one of claims 1, 2, 3, 4, 5, 6, 7 or 8, wherein: The second sublayer includes graphene oxide.

10. A wet gas power generation device according to any one of claims 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein the wet gas power generation device is configured such that the second sublayer is positioned between the first layer and the second electrode, the second layer has a top surface facing the first sublayer and a bottom surface facing the second electrode, and the wet gas power generation device is configured to prevent moisture from entering the bottom surface of the second sublayer.

11. A wet gas power generation device according to any preceding claim, wherein: The second electrode is isolated from moisture.

12. A wet gas power generation device according to any preceding claim, wherein: The second sublayer is adjacent to the second electrode and is electrically connected to the second electrode.

13. A wet gas power generation device according to any preceding claim, wherein: The first sublayer includes an ionic salt.

14. A wet gas power plant according to any preceding claim, wherein: The first sublayer includes a hydrogel.

15. A wet gas power generation device according to any preceding claim, wherein: The first sublayer is doped with charge carriers.

16. A wet gas power plant according to any preceding claim, wherein: The device is configured to absorb moisture from the environment, and the electrical performance is improved in higher humidity environments.

17. A wet gas power generation device, comprising: a first electrode and a second electrode; a functional layer that releases charge carriers to the first electrode and the second electrode; as well as A layer that acts as a moisture reservoir to provide moisture to the functional layer.

18. The wet gas power generation device according to claim 17, wherein: The layer serving as a moisture reservoir to provide moisture to the functional layer is disposed between the first electrode and the second electrode.

19. The wet gas power generation device according to claim 17 or 18, wherein: The functional layer comprises at least two sublayers, a first sublayer being the layer acting as a moisture reservoir and a second sublayer providing charge carriers when provided with moisture.

20. A wet gas power generation device, comprising: a first electrode and a second electrode; as well as a functional layer disposed between the first electrode and the second electrode, the functional layer releasing charge carriers when the power generating core is exposed to moisture; The functional layer includes at least two sub-layers, the sub-layers are stacked between the first electrode and the second electrode (and adjacent layers are electrically connected); Wherein, one of the sub-layers is a polymer sub-layer.

21. The wet gas power generation device according to claim 20, wherein: When the electricity generating core is exposed to moisture, the polymer sublayer acts as a moisture reservoir to adjacent sublayers.

22. A wet gas power generation device, comprising: a first electrode and a second electrode; as well as a functional layer disposed between the first electrode and the second electrode, the functional layer releasing charge carriers when the power generating core is exposed to moisture; The functional layer includes at least two sub-layers, the sub-layers are stacked between the first electrode and the second electrode (and adjacent layers are electrically connected); When the power generating core is exposed to moisture, one of the sublayers that is a polymer sublayer acts as a moisture reservoir to an adjacent sublayer.

23. A power generation core, comprising: A first electrode and a second electrode, and a functional layer located between the first electrode and the second electrode, the functional layer releasing charge carriers when the power generating cell is exposed to moisture.

24. The power generating core according to claim 23, wherein: The functional layer includes at least two sub-layers, the sub-layers are stacked between the first electrode and the second electrode, and adjacent sub-layers are electrically connected.

25. The power generating core according to claim 23 or 24, wherein: When the electricity generating core is exposed to moisture, each of the sub-layers releases charge carriers.

26. The power generating core according to claim 24 or 25, wherein: Each of the sub-layers comprises a different material.

27. The power generating core according to claim 24, 25 or 26, wherein: A first of the sublayers is a polymer sublayer.

28. The power generating core according to claim 27, wherein: The polymer sublayer is one of the following: polystyrene sulfonic acid, sodium polystyrene sulfonate, polyacrylic acid, polyvinyl alcohol, lithium polystyrene sulfonate, potassium polystyrene sulfonate, ammonium polystyrene sulfonate, magnesium polystyrene sulfonate, aluminum polystyrene sulfonate, polystyrene thiol.

29. The power generating core according to claim 24, 25, 26, 27 or 28, wherein: The second sublayer of the sublayers includes one of the following: MXene, oxidized MXene, PVA, PAA, GO.

30. The power generation core according to 29, wherein: A second one of the sublayers is adjacent to the first polymer sublayer.

31. The power generating core according to any one of claims 24 to 30, wherein: A second one of the sub-layers includes a carbon-based material that releases charge carriers when exposed to moisture.

32. The power generating core according to any one of claims 27 to 31, wherein: A first one of the sublayers that is a polymer sublayer is adjacent to and electrically connected to the first electrode.

33. The power generating cell of any one of claims 23 to 32, wherein the first electrode is permeable to moisture.

34. The power generating core according to any one of claims 23 to 33, wherein: The first electrode includes Ag, Zn, Zn plate, Zn foam, Al, Mg, Cu, Ni, Fe or Ti.

35. The power generating core according to any one of claims 24 to 34, wherein: A second sublayer of the sublayers is adjacent to and electrically connected to the second electrode.

36. The power generating cell of any one of claims 24 to 35, wherein the second electrode is isolated from moisture.

37. The power generating core according to any one of claims 24 to 36, wherein: The sub-layers have different moisture absorption properties.

38. The power generating core according to any one of claims 24 to 37, wherein: The moisture absorption characteristics of the sub-layers decrease from the sub-layer adjacent to the first electrode to the sub-layer adjacent to the second electrode.

39. The power generating core according to any one of claims 24 to 38, wherein: When the electricity generating core is exposed to moisture, a first one of the sub-layers that is a polymer layer acts as a moisture reservoir to the adjacent sub-layers.

40. The power generating core according to any one of claims 23 to 39, wherein: The first electrode exhibits an electrochemical reaction when in contact with moisture.

41. The power generating core according to any one of claims 23 to 40, wherein: The first electrode comprises at least one active metal: Al, Cu, Ni, Al, Zn, Zn foam, Mg, Fe or Ti.

42. The power generating core according to claim 23, wherein: The functional layer includes PSSNa.

43. A power generation core, comprising: a first electrode and a second electrode, and a functional layer between the first electrode and the second electrode, the functional layer releasing charge carriers when the power generating core is exposed to moisture; The functional layer includes at least two sublayers, and the sublayers are stacked between the first electrode and the second electrode; When the electricity generating core is exposed to moisture, each of the sub-layers releases charge carriers; wherein a first sub-layer of the sub-layers is a polymer sub-layer and is electrically connected to an adjacent sub-layer.

44. The power generating core according to claim 43, wherein: The first sublayer is PSSNa.

45. The power generating core according to claim 43 or 44, wherein: One of the sub-layers is electrically connected to the second electrode and includes GO.

46. ​​A power generation core, comprising: A first electrode and a second electrode, and a functional layer located between the first electrode and the second electrode, the functional layer releasing charge carriers when the power generation core is exposed to moisture, wherein the functional layer includes PSSNa.

Citation Information

Cited By

  • Silk-screen printing textile-based wet power generation device and preparation method and application thereof

    CN122026745A